Thonzonium bromide suppresses malignant phenotypes of pleural mesothelioma cells in association with reduced KAP1 Ser473 phosphorylation - Dan Song; Jintao He; Qianwen Du; Shaoyang Huang; Wenbing Huang; Zhengliang Li; Zifeng Ruan; Xingguo Liu; Jing Zhang; Wei Xiong (Tissue and Cell, 2027)

Phytochemical profiling of Manglietia chevalieri and its potential in attenuating pulmonary fibrosis: Insights into bioactive constituents - Zi-Jie Long; Mao-Mao Zheng; Yu-Hang He; Bi-Xi Tang; Zhi-Xuan Wang; Xian-Neng Lu; Xi Chen; Jia Li; Yi Zang; Juan Xiong (Phytochemistry, 2027)

Cover crop-specific root-derived biopore structure is associated with biopore sheath bacterial facets in compacted soil columns - Peng Xiong; Guilong Li; Zejun Luo; Hao Li; Zhengfu Yue; Yueming Chen; Xiaolin He; Xiong Fang; Jia Liu; Jingjing Peng (Soil and Tillage Research, 2026)

WNK4 restrains endometrial cancer progression by reprogramming macrophage polarization toward an M1-like phenotype - Jiarong He; Tian Zhang; Menglan Xiong; Jing Zhao; Ziqing Wan; Guang Li; Qi Tian; Pu Zhang; Chuqiang Shu (Molecular Biology Reports, 2026)

Epigenetic silencing of DLEC1 correlates with tumor immune microenvironment and predicts immunotherapy prognosis in multiple cancers - Ruijie Ming; Qi Xiong; Shuh-Ying Tan; Lili Li; Shujie Bao; Jianhua Wang; Lijuan Zhao; Xiaoqian He; Zeze Zheng; Yan Wang; Xiaoyu Liu; Jun Tang; et al. (Human Genetics, 2026)
Cancer remains a major health issue globally, with increasing incidence and mortality rates. While immunotherapy has revolutionized cancer treatment, not all patients benefit, urging the identification of predictive biomarkers. This study utilized public datasets and tumor samples to examine the expression and promoter hypermethylation of DLEC1 in normal and tumor tissues, to evaluate its potential as prognostic and immunotherapy marker. In vitro and in vivo experiments on breast cancer (BrCa) cell lines were conducted to explore the functions and mechanisms of DLEC1 . The prognostic significance of DLEC1 downregulation and its impact on immune cell infiltration and immunotherapy efficacy were analyzed using the GEO and TCGA databases. DLEC1 was frequently downregulated and methylated across multiple cancers. In BrCa, expression of DLEC1 inhibited tumor cell proliferation, induced apoptosis, and activated the interferon lambda1 signaling pathway, indicating its important role as a bona fide tumor suppressor and immunoregulator. High DLEC1 expression correlated with better prognosis in several cancer types and with increased immune cell infiltration. Cancer patients with high DLEC1 expression showed improved overall and progression-free survival under immune checkpoint inhibitor therapies, such as anti-CTLA4, anti-PD1 and anti-PDL1. DLEC1 promoter hypermethylation is a promising biomarker for cancer prognosis and potential immunotherapy response prediction. Its expression and promoter hypermethylation status could thus help to guide clinical treatment strategies for cancer patients, particularly of breast cancer.

Enhanced photothermal catalytic oxidation of cyclohexane over a S-scheme CoAl2O4/WO3-x heterojunction with LSPR effect-induced hot electrons - Kuan Wang; Kai-Xiong Dai; Yu-Rui Chao; Yue Yang; Xin-Peng Li; Zhen-Hong He; Weitao Wang; Huan Wang; Zhao-Tie Liu (Journal of Environmental Chemical Engineering, 2026)

Temperature-assisted continuous ethanol gradient fractionation for modulating the structure characteristics and in vitro digestive properties of debranched normal corn starch - Zihui Xu; Hao Li; Mingju Li; Liyang Zhou; Xiaoyang He; David Julian McClements; Lei Dai; Liu Xiong; Qingjie Sun (Food Chemistry, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

Autogenous dentin graft material promotes bone regeneration involving OPN/CD44-mediated BMSC recruitment - Xin Deng; Jianmin Zhuo; Yanyan Yang; Ziliang Zhou; Jing Li; Rong Rong; Weihong Chen; Jiashen Chen; Siwen Yu; Siyuan Chen; Lu He; Janak Lal Pathak; et al. (Chemical Engineering Journal, 2026)

ADRB2 modulates asbestos-induced pleural mesothelioma progression by influencing IL-17/NF-κB-related inflammatory signalling: An integrated network toxicology, multi-omics and experimental study - Shaoyang Huang; Dandan Gu; Jintao He; Guangsheng Hou; Jundong Wang; Zhengliang Li; Min Yu; Jiangyan Li; Wei Xiong (Chemico-Biological Interactions, 2026)

Chemical constituents from Micromeria biflora and their chemotaxonomic significance - Chen Peng; Xing-Li Zhang; Deng-Li Xiong; Fei-Yan Zhao; Kun Xie; Hong-Ping He; Ming-Ming Li (Biochemical Systematics and Ecology, 2026)

Ferulic acid liposomes improve diabetic EPC angiogenesis by upregulating the AMPK/KLF4/FAM3A pathway - Xiao-ling Zou; You-yuan He; Xi Zhang; Wen-xiao Hu; Si-ying Li; Xiang-nan Liu; Shao-ye Qiao; Ying Wang; Biao Luo; Si-jia Zhao; Qiao Liu; Wu Xiong (In Vitro Cellular & Developmental Biology - Animal, 2026)

Hydro-mechanical coupling between pore pressure and crustal deformation following earthquakes: insights from groundwater tidal response and InSAR analysis - Luoyao Xiong; Guanru He; Zheming Shi; Guangcai Wang; Zhiyu Qi; Peng Ye; Guoying Li (Journal of Hydrology, 2026)

Assessing the impacts of ecotourism on perceived ecosystem services and livelihoods: a case study in the Hani Terraces, China - Zhongde Huang; Degui Fu; Maroof Ali; Zhengchang Ma; Mei Li; Xiong Luo; Anjian He; Yang Bai (Journal of Outdoor Recreation and Tourism, 2026)

OsSultr1;1 and OsZIP4 mediate cadmium uptake and transport in rice: evidence from high and low Cd-accumulators - Xin Qu; Chen He; Bingcai Xiong; Changfu Wu; Haoran Li; Xiaoyan Song; Shufeng Wang; Hongxia Du; Ming Ma (Journal of Hazardous Materials, 2026)

Flooded cultivation improves grain yield and appearance quality while reducing nutritional quality in Shanlan upland rice (Oryza sativa L.) - Xiaoli Huang; Mingsong Liu; Jing He; Jianing Liu; Farooq Shah; Li Xiong; Peng Wang; Zhaojie Li; Qianhua Yuan; Yang Tao; Wei Wu (Food Chemistry, 2026)

Room-temperature photoinduced synthesis of ultrabright silanized polymer dots for ultrasensitive miRNA-21 detection in lung cancer diagnosis - Peipei Hu; Yunpeng Xue; Jianlin Yu; Yang Wu; Haoxuan Xiong; Tingting Miao; Dan Wang; Qinghua He; Yanping Li; Zhenqiang Ning (Chemical Engineering Journal, 2026)

Machine learning-empowered spatial environmental health risk management: Causal inference for sustainable urban agglomeration health equity - Zeduo Zou; Yu Liao; Ye Wang; Ruilin Meng; Yue Gao; Dejian Zhao; Ni Xiao; Ning Liang; Baoyu Chen; Xiuyan Zhao; Xiong He; Hao Yao; et al. (Applied Geography, 2026)

Multi-omics, machine learning, and molecular simulation identify CD44 as a candidate target in endocrine-disrupting chemical–associated thyroid cancer progression - Yifan Hu; Keshu Liu; Ting Chen; Zhizhen He; Shuang Li; Wu Hu; Qiuyang Fu; Xiong Chen (Molecular Diversity, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Corrigendum to “A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice” [Sci. Bull. 71(11) (2026), 2701-2705] - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Direct photoreforming of polylactic acid waste into valuable fuels via interface-activated superoxide radicals - Dongpo He; Ziyao Zhou; Fangming Zhao; Zheng Li; Jie Xiong; Jinyu Ding; Yang Wu; Liang Chen; Meng Zhou; Jun Hu; Junfa Zhu; Wensheng Yan; et al. (Science Bulletin, 2026)

Unexpected V-shaped temperature dependence of methane fluxes informing its sources in a megacity of China - Ruilin Zhang; Yibo Huangfu; Bin Yuan; Xiaoxiao Zhang; Xianjun He; Thomas Karl; Yang Ding; Hongjuan Li; Kyung-Eun Min; Ying Xiong; Xiao-Bing Li; Zhe Peng; et al. (Science Bulletin, 2026)

Corrigendum to “Assessing the impacts of ecotourism on perceived ecosystem services and livelihoods: a case study in the Hani Terraces, China” [Journal of Outdoor Recreation and Tourism 55 (2026) 101077] - Zhongde Huang; Degui Fu; Maroof Ali; Zhengchang Ma; Mei Li; Xiong Luo; Anjian He; Yang Bai (Journal of Outdoor Recreation and Tourism, 2026)

Biochemical characterization of a novel ochratoxin A-detoxifying amidohydrolase from Terribacillus saccharophilus JX-8 and its application in grape juice and wheat flour - Bin Liu; Miaohuan Xiong; Wanlin Sun; Huipeng Wu; Jialu Li; Yuqi Wang; Qing Wang; Jian He; Xuelan Chen (Food Research International, 2026)

Membrane-based advanced oxidation processes for water and wastewater treatment: Advances, trade-offs, and challenges - Caihong Liu; Chi Xiong; Hai Liang; Kun Yang; Andreia F. Faria; Liu Yang; Amauri J. Paula; Hongtao Li; Dan Song; Qiang He; Jun Ma (Chemical Engineering Journal, 2026)

Source-specific oxidative potential and health risks of PM2.5-bound toxic elements in Xiamen Port: Insights into ship emission contributions - Si-Min Zhao; Qi-Yu Miao; Jia-Min Li; Xin-Ye Wu; Bing-Qi Jiang; Li-Xiong He; Yi-Jing Liu; Zhi Huang; Chung-Shin Yuan; Shui-Ping Wu (Atmospheric Pollution Research, 2026)

Effects of population size and sex ratio on reproduction, sex-specific survival, and population growth in spider mite Tetranychus urticae Koch - Peng Zhou; Yujie Zhang; Xiong Zhao He; Chunyun Huang; Qianqian Wu; Xinyue Wang; Jiahao Li; Chen Chen (Experimental and Applied Acarology, 2026)

The mixed cover crops and nitrogen fertilization decrease the soil microbial dormancy - Simeng Wang; Xue Zhao; Wanyu He; Jieying Wang; Minghui Meng; Xiya Xiong; Min Xie; Guangjin Wu; Qilong Du; Lin Li; Guangxi Liu; Jun Wang; et al. (Plant and Soil, 2026)

Single-cell sequencing reveals the co-option of epithelial structural programs by macrophages in teleost granulomas - Zhengyang Zhou; Jinlai Gu; Zhengran Jian; Jie He; Zhendong Zhong; Quanxin Xiong; Min Qi; Yuanchang Gao; Sheng Lian; Shangjie Bai; Chenwang Lu; Linfeng Kuang; et al. (Aquaculture, 2026)

Corrigendum to “Effects of betaine on viability, apoptosis, function protein expression and oxidative status in heat-stressed IEC-6 cells” [J. Therm. Biol. (2022) 103348] - Shiang Sun; Qirun Yin; Bing Li; Yafei Deng; Jing Li; Yongjie Xiong; He Shaojun (Journal of Thermal Biology, 2026)

Machine learning and multi-dimensional transcriptomics reveal the key molecular network of benzo(a)pyrene/NNK in promoting laryngeal cancer and develop prognostic models - Yifan Hu; Zhizhen He; Shuang Li; Baoai Han; Xiuping Yang; Xiong Chen (Environmental Pollution, 2026)

Power-Load Characteristics of Fixed Oscillating Water Column Chambers for Potential Integration with Offshore Wind Jacket Foundations - Guohu Xie; Qinzhang Li; Fangyuan Yi; Rongquan Wang; Gen Xiong; Dezhi Ning; Ben He (Journal of Marine Science and Engineering, 2026)
The integration of wave energy converters with offshore wind foundations offers a potential route to improving the utilization of offshore renewable energy infrastructure. This study numerically investigates the power-load characteristics of fixed oscillating water column (OWC) chambers intended for potential installation near offshore wind jacket foundations. A preliminary jacket comparison is first used to delimit the scope, after which the main parametric study is performed on isolated OWC chambers so that pneumatic response and local chamber loads can be compared consistently. The simulations are conducted under regular waves with a wave height of H = 0.05 m, a water depth of h = 1.6 m, and wave periods of T = 0.9–1.7 s. Three baseline geometries, namely cylindrical, sandglass-shaped, and bottle-shaped OWCs, are first screened in order to identify the most suitable reference chamber family. The cylindrical chamber is then retained as the reference configuration for subsequent local parameter studies of the frustum-contraction parameter D2 and the front-wall draft d2. The results indicate that the geometric effect is strongly dependent on the incident-wave period. The sandglass-shaped and bottle-shaped chambers can enhance short-period pneumatic power or reduce loads at longer periods, whereas the cylindrical chamber provides a more consistent reference response over the tested range. Under the wave conditions adopted in this study, further analysis reveals that D2 exerts a non-monotonic tuning effect varying with wave period. For the selected frustum-shaped configuration, increasing d2 reduces hydrodynamic loads yet simultaneously weakens pneumatic power output and CWR. Because the air phase is treated as incompressible and the orifice represents an orifice-only damping condition rather than a turbine-controlled PTO system, the reported Pe should be interpreted as a pneumatic/hydrodynamic comparison metric and not as wave-to-wire electrical power. The conclusions are therefore positioned as regular-wave geometry-tuning trends for the present model scale rather than as full coupled jacket-OWC design rules.

In vitro nephroprotective indolizidine alkaloids from marine-derived Streptomyces sp. KIB629 - Xiaowei Guo; Lei Wang; Xin He; Bing-Yi Xu; Jun-Jie Zhang; Jian-Ping Huang; Wei Li; Sheng-Xiong Huang; Jing Yang; Ya-Tuan Ma (Natural Product Research, 2026)

Structural and dynamic insights into SPDT for phosphorus allocation in rice - Haitao He; Yan Liu; Jie Zhang; Xiaofeng Zheng; Lihuan Jiang; Zhangmeng Du; Jiaqi Zuo; Shuo Cao; Xuemei Peng; Zhiwen Zheng; Kun Li; Cuicui Shen; et al. (Science China Life Sciences, 2026)

Permeability evolution driven by the suffusion process in silica sands under cyclic loading: Mathematical model and experimental verification - Feng Gao; Jinbao Zhang; Sheng Zhang; Xiaobin Li; Hongling Xiong; Xuzhen He (Transportation Geotechnics, 2026)

A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Across-arc variations of potassium isotope compositions in a fluid-dominated subduction zone and implications for global potassium recycling - Ying-Yu Xue; Haiyang Liu; He Sun; Haiou Gu; Shichao An; Gerhard Wörner; Guozhi Xie; Maoqiang Yan; Dapeng Li; Yuxin Xiong; Fanfan Tian; Weidong Sun (Geochimica et Cosmochimica Acta, 2026)

Dual covalent–hydrogen-bond networks enable synergistic thermo-mechanical performance and durability in polyimide films - Luling He; Xiong Li; Jiamei Liu; Yu Zhang; Na Song; Tongle Xu; Peng Ding (Chemical Engineering Journal, 2026)

Beyond magnetic-field enhanced peroxymonosulfate activation: Interfacial restructuring of nanoscale Fe0 for efficient contaminant degradation - Jingyang Luo; Ran Yu; Xinyi Liu; Chao He; Fuqiang Liu; Jianglei Xiong; Shilong Jiang; Song Cheng; Yiping Li (Chemical Engineering Journal, 2026)

Integrating Biotic and Abiotic Measures Enhances Early Ecosystem Functionality in Degraded Grasslands - Yang Lei; Chang-Ning Li; Tuo Yao; Yakov Kuzyakov; Chen Zhang; Shan-Mu He; Jia-Li Chai; Jie Bai; Yi-Xin Zhang; Shuang-Xiong Li (Journal of Soil Science and Plant Nutrition, 2026)

Metabacillus mesotrionivorans sp. nov., a Mesotrione‑Degrading Bacterium Isolated from Cornfield Soil - Jialu Li; Huipeng Wu; Miaohuan Xiong; Jian He; Zhiming Wu; Bin Liu; Haiyan Ni (Current Microbiology, 2026)

Study on the outbreak characteristics and mechanisms of estuarine and offshore harmful algal blooms in the East China Sea - Shan Wang; Xizhen Liu; Siyang Chen; Wenbin Yin; Wei Xiong; Hongliang Li; Yuqing He; Jiliang Xuan (Frontiers in Marine Science, 2026)
Harmful algal blooms (HABs) occur frequently in the coastal waters of the East China Sea and exhibit pronounced spatiotemporal heterogeneity under complex hydrodynamic conditions. However, systematic comparative studies on the driving mechanisms of HABs under different hydrodynamic regimes remain limited. Based on in-situ observations from 2015 to 2020 and a high-resolution coupled physical–ecological model, this study comparatively investigated HAB developmental characteristics and environmental driving mechanisms in two typical coastal regions of the Zhejiang coast: the near-estuary Shengsi area, dominated by Changjiang Diluted Water, and the far-estuary Cangnan area, primarily controlled by coastal current systems. Statistical analyses, Mann–Kendall trend tests, and principal component analysis were applied to identify the dominant environmental controls associated with HAB outbreaks. HABs in Shengsi occurred sporadically from May to September and were mainly characterized by short duration (≤7 days) and small-to-medium spatial scales. In contrast, HAB outbreaks in Cangnan were strongly concentrated in May–June (91% in simulations and 84% in observations), with a higher frequency of large-scale events (duration >20 days; area >400 km²). Mechanistic analyses indicated that HAB dynamics in the nutrient-poor but hydrodynamically stable Cangnan waters were primarily regulated by hydrodynamic processes. An initial increase in current velocity (~0.067 m/s) promoted the transport and accumulation of nutrients (nitrate +0.8 mmol/L; phosphate +0.06 mmol/L), whereas the subsequent rapid weakening of currents, observed in 79.8% of HAB events, enhanced water-column stability and favored algal aggregation. The turning point of current velocity generally preceded the chlorophyll-a peak by approximately one day. Principal component analysis further confirmed the dominant role of physical regulation in Cangnan, where the first principal component explained 56.44% of the total variance. In contrast, Shengsi exhibited sufficient nutrient supply but relatively unstable hydrodynamic conditions due to interactions among multiple water masses. Except for seawater temperature, most environmental variables showed no statistically directed changes before and after HAB outbreaks, with increase–decrease probabilities close to 50%. The first principal component explained only 28.94% of the total variance, indicating a highly multifactor-driven HAB system. This study reveals substantial differences in HAB formation mechanisms between near-estuary and far-estuary systems in the East China Sea. HAB outbreaks in Cangnan are strongly associated with hydrodynamic stability, whereas HABs in Shengsi are jointly regulated by multiple environmental factors. These findings improve the understanding of HAB dynamics under complex coastal hydrodynamic backgrounds and provide a scientific basis for region-specific HAB forecasting and early-warning strategies along the Zhejiang coast.

Structural decomposition enables multi-omics dissection of common and organ-specific aging - He Huang; Yi Li; Qinglin Song; Liyun Yuan; Yuqi Yang; Minwei Zhu; Renliang Sun; Yue Hu; Chenyihang Xiong; Ting Ni; Yun Liu; Andrés Ruiz-Linares; et al. (Science China Life Sciences, 2026)

Inhibitory effect of pulsed electric field pretreatment on acrylamide formation in air-fried French fries and its mechanism - Jian Li; Yue-Wei Huang; Yi-Tong Li; Shi-Yin Luo; Wei-Yan Xiong; Jin-Hua Wang; Jun-Hu Cheng; Ting-Shi He; Xin-An Zeng (Food Research International, 2026)

Unraveling hydration and physicochemical property modulation in potato starch gels through multiscale structural orientation induced by uniaxial stretching–drying - Liu Xiong; Yuting He; Xianzhi Liu; Man Li; Zhongxiu Wang; Shengtian Zhang; Qingjie Sun (Food Hydrocolloids, 2026)

Warming altered the variational effects of microplastics and leachate from biodegradable mulch films on organic carbon transformation in riparian zones - Wenjuan He; Si Liu; Yalan Xiong; Jinying Hu; Zhexi Liu; Yuanyuan Li; Chenhong Wu; Mengyu Ma; Lin Shi; Jinhui Huang (Environmental Pollution, 2026)

Natural polysaccharides for alleviating heavy metal toxicity — Recent advances and future prospects - He Liu; Yanru Li; Qiming She; Shenglong Yang; Jiameng Sun; Xinyi Zhi; Kaixuan Mao; Shixin Song; Lei Yu; Boyu Xiong (Carbohydrate Polymers, 2026)

Sublethal effects of typical neonicotinoids exposure on Drosophila melanogaster: Insights from phenotypic abnormalities to molecular mechanisms - Fang Li; Chen Yan; Yitian Min; Wenbin Li; Siying He; Weiping Xiong; Zhuotong Zeng; Biao Song (Pesticide Biochemistry and Physiology, 2026)

Construction of carbon-based composites for electrochemical antibiotic sensing application: A review - Jiayin Li; Yao Chen; Meng Xiong; Jun Liu; Quanguo He (Journal of Environmental Chemical Engineering, 2026)

Polystyrene microplastics impaired decidualization in mice via oxidative stress and inflammation and disrupted the reproductive function of their female offspring - Weike Li; Boyin Tan; Jun Xiong; Jiani Diao; Jing Wang; Jing Long; Zhenyin Chen; Yuguang He; Xuemei Chen; Fei Han; Fangfang Li; Junlin He; et al. (Journal of Environmental Sciences, 2026)

Integrated HTO@fiber interfacial evaporator for concurrent photovoltaic cooling, lithium extraction, and desalination - Qihao He; Yang Xiao; Da Li; Guangzhao Qin; Xiong Zheng (Desalination, 2026)

Compensation for the initial capacity loss in lithium-ion batteries via controlled electrolyte decomposition at cathode - Jiajia Zhu; Tingyu Zhao; Qiuyu Jia; Hexiang Lan; Longfei An; Yuqi Jiang; Aiping Jin; Weiming Wang; Luying He; Jun Xiong; Junjun Peng; Ming Li; et al. (Chemical Engineering Journal, 2026)

Myricetin alleviates myocardial infarction-induced cardiac fibrosis in mice by upregulating SIRT1 to inhibit TGF-β1/Smad2/3 signaling - Xiaojv Xiong; Rui Dai; Guangji Wang; Xin Guo; Qin He; Jijun Liu; Gang Chen; Pan Lu; Shuang Li; Denghai Liu; Jinhua Liu; Manhua Chen (Molecular & Cellular Toxicology, 2026)

Host size and parasite density impact on the efficacy and reproductive output of Pyemotes zhonghuajia, a biological control agent of potato tuber moth - Chenming Xiao; Xiong Zhao He; Xuelin Li; Di Fan; Long Zhang; Chengxu Wu; Maofa Yang; Jifeng Hu; Guy Smagghe; Jianfeng Liu; Fangling Xu (Experimental and Applied Acarology, 2026)

Predatory performances and adaptive strategies of Eocanthecona furcellata (Hemiptera: Pentatomidae) to the larvae of Phauda flammans (Lepidoptera: Phaudidae) - Jian-Zhong Ning; Da-Xing Lu; Xiong Zhao He; Xiao-Yun Wang; Kai Lin; Jun Li; Xia-Lin Zheng (Applied Animal Behaviour Science, 2026)

Characterization of rumen-derived Enterococcus faecium strains and their effects on fermentation quality and in vitro digestibility of rice straw silage - Xuxiong Tao; Haitian Li; Xiong Li; Wei Deng; Xin He; Qianhui Zhang; Junfeng Li (Animal Feed Science and Technology, 2026)

Agroforestry balances plant–soil–microbe–enzyme interactions and improves its connectivity and homeostasis: Evidence from C:N:P stoichiometric networks - Qi-Wen Xu; Meng-Die Feng; Tian-Yang Li; Lin Xiong; Bo-Yu Ren; Yan-Zheng He; Bing-Hui He (Agriculture, Ecosystems & Environment, 2026)

Two new polyketide derivatives isolated from the mangrove-derived fungus Aspergillus sp. GXNU 2Y10 - Fan He; Wenjun Li; Youquan Wei; Jiao Wu; Congli Lei; Zhenlan Li; Zheng Xiong; Xishan Huang (Natural Product Research, 2026)

Automated rice mapping under diverse cropping patterns and establishment methods by integrating phenological knowledge and synergy of optical and SAR imagery - Xingrong Li; Gaoxiang Yang; Meng He; Yuan Xiong; Leilei Liu; Hifza Mariam; Iftikhar Ali; Chongya Jiang; Xia Yao; Yan Zhu; Weixing Cao; Tao Cheng (Remote Sensing of Environment, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Deinococcus sp. NH1 enhances cadmium tolerance in rice by modulating rhizosphere microbiome and plant metabolism - Dandan Li; Zhikai Diao; Aiping Shu; Shurong Gan; Wenxue Zhang; Yichi Zhang; Li Xiong; Daimin Wei; Longxin He; Wenchong Shi; Gang Sun; Fusheng Yuan; et al. (Journal of Hazardous Materials, 2026)

Spatiotemporal evolution of trade-off/synergy relationships and bundles in ecosystem services in Fujian, China: An integrated PLUS-InVEST-SOM framework - Zhihui Lin; Zhu He; Chenjie Ye; Yanan Li; Haolan Liu; Shanshan Ding; Xiaoyang Qiao; Jiayu Xiong; Jiakang Huang; Xisheng Hu; Jian Li (Journal of Cleaner Production, 2026)

Corrigendum to “Optimization of rice husk ash concrete design towards economic and environmental assessment” [Environmental impact assessment review 103 (2023) 107229] - Bin Xi; Ning Zhang; Huabo Duan; Jintao He; Guanghan Song; Huanyu Li; Xiong Shi (Environmental Impact Assessment Review, 2026)

Behaviorally inspired by blue-whale throat-pleats during filter feeding: A thermoresponsive hydrogel for achieving efficient solar-driven cyclic water release and purification - Yan-Shu Xiong; Mei Li; Tanli Lu; You-Ya Sun; Hai-Qin Lu; Wen Li; He Liu; Zhanqian Song (Chemical Engineering Journal, 2026)

Vitamin C rescues embryonic developmental arrest caused by maternal Kdm2a deficiency via regulating PTEN/PI3K/AKT axis - Qinhui Yang; Yumian Xie; Ying Cen; Ruilan Zeng; Yuan Li; Xupeng Li; Yan Xiong; Honghong He; Shi Yin; Jian Li; Xianrong Xiong (Theriogenology, 2026)

Janus carbonaceous assembly of biomimetic wettability-gradient air electrode for optimizing zinc-air battery kinetics - Yafei Zhao; Xingmei Guo; Hanzhen Li; Weidong He; Qianqian Fan; Zhongyao Duan; Shenglin Xiong; Qinghong Kong; Junhao Zhang (Science Bulletin, 2026)

Structural integrity of the teleost granuloma: a macrophage barrier driven by coordinated activation of junctional, cytoskeletal and extracellular matrix gene networks - Zhengyang Zhou; Linfeng Kuang; Chenwang Lu; Jie He; Zhengqiang Yu; Zhendong Zhong; Quanxin Xiong; Min Qi; Jinlai Gu; Yuanchang Gao; Sheng Lian; Zhengran Jian; et al. (Fish & Shellfish Immunology, 2026)

Interactions among microplastics, spilled oil and dispersant: Impacts of marine environmental conditions - Xinping Yu; Xiaoan He; Zhixin Qi; Miao Yang; Xishan Li; Deqi Xiong (Marine Pollution Bulletin, 2026)

Nickel-iron Prussian blue composite membranes with ion-sieving channels for targeted cesium ion capture in aquatic systems - Siqi He; Zhuoran Yi; Sakil Mahmud; Weiyu Li; Yupeng Li; Zhixuan Luo; Weiting Wang; Yimeng Feng; Gaosheng Zhang; Zhu Xiong (Water Research, 2026)

Greenhouse gas emissions from black soldier fly composting of silver and silver sulfide nanoparticle-enriched sludge - Jingtao Wu; Lei Xiong; Yuantong Yang; Cui Li; Peng Mao; Qingqiu Zhou; Guangcan Yu; Xingyun Huang; Rajeshwar Dayal Tyagi; XinXing He; Jonathan W.C. Wong (Water Research, 2026)

Long-term intercropping mitigates warming-induced carbon loss via enhancing microbial and substrate resistance - Wei Wang; Yang Wang; Jian-Ming Li; Meng-Ying Li; Peng He; Yongxing Cui; Sheng-Jun Ji; Wen-Ying Wang; Levis Kavagi; Muhammd Ashraf; Yinglong Chen; Matthias C. Rillig; et al. (Soil Biology and Biochemistry, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Hydrogeochemical evolution mechanisms in a confined well induced by the May 6, 2018, Ms 5.3 Chengduo Earthquake, Qaidam Basin, northwest China - Luoyao Xiong; Guangcai Wang; Zheming Shi; Fu Liao; Pengpeng Zhou; Guanru He; Igor Alexandrov; Ivan Bragin; Guoying Li (Journal of Hydrology, 2026)

Simultaneous transformation of tetracycline and nitrogen (ammonium/nitrite) by Sphingobacterium kyonggiense T8: Performance, pathway, genomics, and mechanisms - Yifei Leng; Yangqi Peng; Huan He; Ting He; Fengyi Chang; Wen Xiong; Zhu Li (Journal of Hazardous Materials, 2026)

Unveiling ecological risks of organophosphorus pesticides at environmental levels: Cyanobacterial bloom stimulation and toxin accumulation - Siyuan Li; Yitao Ma; Xianyao Zheng; Guangzhou He; Jinrui Xiong; Hao Lu; Zhixiang Xu; Xuejun Pan (Journal of Hazardous Materials, 2026)

Recrystallization and orientation competition via hot extrusion in n-type Bi2Te3 alloys for advanced power generator - Tao Xiong; Hailong He; Ge Tian; Yi Wu; Youqun Li; Chunping Niu; Feng Jiang; Chenhao Ren; Mingzhe Rong (Chemical Engineering Journal, 2026)

ARC-18 Alleviates Alzheimer-like Pathology and Cognitive Deficits via AdipoR1-Mediated Activation of Autophagy and Modulation of APP Processing - Shangming Li; Bocheng Xiong; Nan Xu; Lulin Nie; Kaiwu He; Guiliang Zhang; Chongyang Chen; Zaijun Zhang; Maggie Pui Man Hoi; Xifei Yang (Molecular Neurobiology, 2026)

Groundwater level prediction in urban karst regions: The comparison of ensemble learning and deep learning models by considering climate conditions - Xiaoqing Song; Ruihan Xiong; Zhenzhu He; Danyuan Luo; Shuyi Li; Ying Wang; Qin Peng; Shilong Yang; Yuxuan Fang; Aiguo Zhou; Xu Guo; Hanxiang Xiong (Urban Climate, 2025)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Puerarin alleviates liver injury induced by heat-stress through regulating oxidative stress and apoptosis in broilers - Guangqing Xu; Feiyang Ma; Yan Li; Jiajun Miao; Xueqi Zhang; Yongjie Xiong; Shaojun He (Journal of Thermal Biology, 2025)

Synergistic enhancement of tetracycline photodegradation in 5 % Ce-doped Bi₂O₃–Co₃O₄/C: Oxygen vacancy-mediated band engineering and singlet oxygen pathway optimization - Xiaoqing Wang; Weiyi Li; Junhao Zhang; Jiangman Zheng; Tuo Li; Cong Du; Xuan Luo; Zhitao Ai; Chennan He; Shanjun Mao; Rongbo Zheng; Qing Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Molybdenum disulfide regulates the transformation of antibiotic resistance genes under simulated light/dark conditions: Role of bacterial oxidative stress and metabolic reprogramming - Yitao Ma; Zhixiang Xu; Siyuan Li; Hao Lu; Jinrui Xiong; Keying Chen; Guangzhou He; Longlong Miao; Bin Huang; Xuejun Pan (Journal of Environmental Chemical Engineering, 2025)

High-efficiency photocatalytic NO removal enabled by dual-ligand modulated assembly of photosensitive TCPP on defective NH2-UiO-66 - Youzhou He; Shuying Gong; Pengfei Zhu; Lijie Zhou; Ning Li; Lin Chen; Xiaoli Xiong; Li Wen; Chenghua Zhang; Yongcheng Feng; Bowen Lei; Xingyan Liu (Journal of Environmental Chemical Engineering, 2025)

Encapsulation of Lactiplantibacillus plantarum subsp. plantarum in oil-phase gels O/W high internal phase emulsions: Improvement of storage stability and gastrointestinal viability - Enjing Huang; Ziling Li; Fangyuan Zhou; Qinyu Chen; Jiayong He; Xiangyuan Xiong; Youfa Xie; Hongxia Gao; Liqiang Zou (Food Chemistry, 2025)

Metal-bridged self-assembly of recognition-functionalized MCOFs for ultrasensitive photoelectrochemical sensing of perfluorooctanoic acid - Xionghui Ma; Wenwen Cao; Rui Chen; He Yu; Chaohai Pang; Zhongsheng Yi; Yuhao Xiong; Bingjun Han; Zhi Xu; Jianping Li; Shuhuai Li (Chemical Engineering Journal, 2025)

Structure-optical activity relationship of chiral helical gold nanorods and their application in alkaline phosphatase detection - Shuai Wen; He Feng Shi; Can Nan Zhao; Ying Ying Xiong; Liang Tong Li; Qiu Yue Liu; Chen Liu; Qiu Sha Li; Wei Wang; Jian Wang (Chemical Engineering Journal, 2025)

An electrospun nanofibrous membrane dressing composed of gallium-curcumin nanoparticles encapsulated by covalent organic framework with antibacterial and antioxidant abilities for enhanced wound healing and recovery - HaoXian He; JinYong Xiong; LongSheng Pei; LongFei Miao; YongHai Song; LiMin Liu; Li Wang (Chemical Engineering Journal, 2025)

Multi-level cognitive state classification of learners using complex brain networks and interpretable machine learning - Xiuling He; Yue Li; Xiong Xiao; Yingting Li; Jing Fang; Ruijie Zhou (Cognitive Neurodynamics, 2025)

Deep learning-based tunnel advance geological forecast for polygon targets via regional GPR data - Ting-wei Yang; Jing-he Li; Ye-hui Cao; Bin Xiong; Liu-ye Wei (Applied Geophysics, 2025)

DEM contact parameters of rice seed for mechanical seeding performance analysis - Shun Zhang; Zhaoyang Cai; Hailong He; Fuming Kuang; Wei Xiong; Dequan Zhu; Zhaodong Li; Mehari Z. Tekeste (Biosystems Engineering, 2025)

Bifidobacterium animalis subsp. Lactis A6 alleviates comorbid constipation and depression by rebalancing tryptophan metabolism - Jian Wang; Yimei Ren; Juan Chen; Shanbin Chen; Xiaoxia Li; Jianwen Chen; Xifan Wang; Lijun Li; Liang Zhao; Yixuan Li; Qi Zhang; Wei Xiong; et al. (Science Bulletin, 2025)

Environmental stressor-induced functional and expression dynamics of glutathione S-transferase genes in bees - Yaohui Li; Linxuan Xie; Xiangyou Tang; Yongyan He; Huali Song; Ruyi Xiong; Baishun Hu; Zhengang Ma; Zeyang Zhou; Jinshan Xu (Pesticide Biochemistry and Physiology, 2025)

Soil type-mediated root and leaf architectural modifications outweigh cadmium bioavailability in governing cadmium accumulation in rice - Gaoxiang HUANG; Jinbao ZHANG; Changfeng DING; Zhongyang XIONG; Jia LIU; Jingru HE; Haoyuan LÜ; Mingjun DING; Peng WANG; Yinghui JIANG; Lijun ZHOU; Zhenling LI (Pedosphere, 2025)

The fate, impacts and potential risks of photoaging process of the microplastics in the aqueous environment - Jing Tong; Siying He; Xiaoming Huang; Xin Li; Xiaodong Nie; Zhengyang Li; Zhongwu Li; Weiping Xiong (Journal of Contaminant Hydrology, 2025)

Integrating aquifer vulnerability and explainable machine learning for spatial prediction of groundwater fluoride - Hanxiang Xiong; Yi Li; Ruihan Xiong; He Xiong; Jiayao Tan; Shilong Yang; Hanting Liu; Xiaoqing Song; Xu Guo (Groundwater for Sustainable Development, 2025)

Synergistic fermentation of cottonseed meal using Lactobacillus mucosae LLK-XR1 and acid protease: Sustainable production of cottonseed peptides and depletion of free gossypol - Liangkang Lv; Fengliang Xiong; Shiteng Pei; Shanshan He; Baiou Li; Lijian Wu; Zhijun Cao; Shengli Li; Hongjian Yang (Food Chemistry, 2025)

Yeast protein as a sustainable fat replacer in reduced-fat mayonnaise: Impact on rheological properties, emulsion stability, and microstructure - Yaqiu Kong; Ruotong Guo; Jian Xiong; Pei Li; Chunlei Ma; Yiyuan He; Qilin Huang (Food Chemistry, 2025)

Unraveling the combined impacts of pristine and aged polyethylene microplastics and the ciprofloxacin antibiotic on sediment microbial communities and ecological functions - Shudian Peng; Siying He; Weixiang Li; Wenyi Feng; Min Hu; Zhaohui Yang; Weiping Xiong; Hui Li (Environmental Pollution, 2025)

Thermo-responsive regeneration of graphene-based ion-imprinted polymer for sustainable lead capture: DFT-guided design and phase transition recovery - Siqing Ye; Shunfei Li; Xintao Yang; Ying Xu; Yi Zhang; Hongxing He; Mingyang Xiong; Ni Yang; Changgen Feng; Zhifeng Nie (Desalination, 2025)

MWCNT-OH/PDMS elastomer-based microwave absorber with high-performance thermal stability and mechanical sensing properties - Jialiang Chen; Kaixi Bi; Shuqi Han; Hao Liu; Wenjun He; Yifan Li; Guangchen Yin; Wenqi Xiong; Linyu Mei; Xiujian Chou (Chemical Engineering Journal, 2025)

Jaagichlorella menglunensis sp. nov. (Watanabeales, Chlorophyta), a new coccoid green alga isolated from China - Huiyin Song; Rongli Guan; Tian He; Langyue Zhang; Tiantian Li; Junfei Zhou; Yuxin Hu; Shuyin Li; Feng Liu; Lun Li; Na Zhang; Huafeng Xiao; et al. (Journal of Oceanology and Limnology, 2025)

Global Change Alters the Abundance and Community Structure of Arbuscular Mycorrhizal Fungi and Influences Plant Mycorrhizal Benefit - Ai‐Tian Ren; Meng‐Li Wang; He‐Miao Gao; Bede S. Mickan; Long‐Yi Yuan; Si‐Kun Liu; Shao‐Cong Zhang; Lynette K. Abbott; You‐Cai Xiong; Fei Mo (Global Ecology and Biogeography, 2025)
Aims Arbuscular mycorrhizal (AM) fungi play critical roles in ecosystem services and exhibit sensitivity to global change factors (GCFs). However, the interactive effects of multiple GCFs on AM fungal communities, and whether changes in AM fungal communities have a feedback effect on plant–mycorrhizal benefits under global change remain poorly understood. Location Global. Time Period 1990 – 2022. Major Taxa Studied Arbuscular mycorrhizal fungi; arbuscular mycorrhizal plant hosts. Methods We synthesised 1646 observations of arbuscular mycorrhizal (AM) fungal communities from field experiments to evaluate how manipulated GCFs affect their abundance and community structure and to determine the potential consequences for outcomes of plant–mycorrhizal fungal relationships. Results The interactive effects among GCFs were mainly additive rather than synergistic or antagonistic. AM fungal diversity was not consistently sensitive to the individual effects of GCFs; however, a significant shift in community structure occurred under individual or concurrent GCFs. When multiple factors were imposed simultaneously, their negative effect on AM fungal colonisation was strengthened, while their effects on community structure were diminished. Moreover, plant performance was closely linked to changes in abundance and community structure of AM fungi under GCFs. Experimental duration and environmental variables emerged as the most important predictors of AM fungal responses to GCFs. Conclusions Reordering or replacement of AM fungal species has been identified as the key mechanism driving community responses to GCFs. Our study highlights the need to monitor AM fungal community structure and associated functional consequences for plant communities under ongoing global change.

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

Three-dimensional mesoporous MnO2 as an active cage for efficient adsorption and combustion of toluene - Xiaodan Wang; Xiaolei Hu; He Zhang; Liyang Dong; Wei Zhang; Xuefei Chen; Cheng Li; Lizhi Wang; Chunrong Xiong (Journal of Environmental Chemical Engineering, 2025)

Insights into the chemical composition and molecular structure of asphalt: guiding material design and performance optimization - Kun Xiong; Maria Chiara Cavalli; Aleksandra Kuksova; Yinzhang He; Xiangqian Ye; Jiupeng Zhang; Rui Li; Dongliang Hu (Fuel, 2025)

Elucidating the mechanism of dibutyl phthalate on Alzheimer's disease through network toxicology, molecular docking and validation in mouse neuroblastoma cells - Jing Zi; Xinlong Li; Qianqian Cao; Yifan Hu; Zhichang Ran; Yanliu Li; Jiayuan He; Xiaoyu Wang; Guo Cheng; Jingyuan Xiong (Food and Chemical Toxicology, 2025)

Microbially induced phosphate precipitation disentangles sludge retention time trade-off enabling efficient phosphorus removal with minimal sludge discharge in aerobic granular sludge - Peng Bi; Xiaohui Yan; Yueying Song; Hebin Miao; Hui Sun; Ying Han; Long Chen; Kangxin Yan; Mingyang Li; Fan Xiong; Jingwei Ma; Qiulai He (Chemical Engineering Journal, 2025)

Adaptation of anammox bacteria in granular sludge under the different temperature rhythms - Yu-Tong Xiong; Zhuo-Li Yan; Jian-Hong He; Shao-Yang Liu; You-Peng Chen; Jin-Song Guo; Fang Fang; Peng Yan (Chemical Engineering Journal, 2025)

Facial feature-based interpretable machine learning models predicting human thermal comfort: Insights from young people with different BMIs - Mengyuan He; Hong Liu; Fengwei Xiong; Risto Kosonen; Simo Kilpeläinen; Minzhou Chen; Panu Mustakallio; Peiping Zheng; Baizhan Li (Building and Environment, 2025)

Fine particulate matter exacerbates asthma by activating STC2-mediated mitophagy through METTL3/YTHDF2-dependent m6A methylation - Yao Liu; Guoping Li; Anying Xiong; Jiliu Liu; Ruitong Zeng; Lei Zhang; Junyi Wang; Manling Jiang; Jie Gao; Ying Xiong; Xiang He (Journal of Hazardous Materials, 2025)

Integrated analyses of the Ediacaran-Cambrian boundary sequence in northern Gondwana (Anti-Atlas platform, Morocco) - Yiwei Xiong; Bo Chen; Xiaojuan Sun; Kai Chen; Ibtissam Chraiki; Aihua Yang; Chunlin Hu; zhixin Sun; Bing Pan; Chuan Yang; Tianchen He; Miao Lu; et al. (Gondwana Research, 2025)

Recycling metal ions from hot-dip galvanizing wastewater to high-value MOFs: From removal of environmental disturbance via hydrothermal to metal resources - Yi He; Huan Xiong; Bifang Zheng; Li Li; Shujie Wang; Shuangqin Tian; Lihong Tang (Desalination, 2025)

MOF-based hypocrellin composite nanomaterials as advanced plant-derived photosensitizers for multimodal therapy - Ying'’ao Wu; Yanjun Guo; Kaijie Feng; Miao Li; Hongxue Li; Jiasheng Wu; Pengfei Wang; Rungong Yang; Xiao He; Xiong Yin; Min Li (Chemical Engineering Journal, 2025)

The conservation of migratory shorebirds needs to account for the different habitat selection patterns across species and between day and night - Shen Zhang; Xiaotong Ren; Ziyin Xiong; Tao He; Kar-Sin Katherine Leung; Wenjie Xue; Li Tian; Lifeng Zhuang; Yi-Chien Lai; Chia-Hsiang Lin; Chi-Yeung Choi (Biological Conservation, 2025)

Quantifying the major sources of nitrate in PM2.5 in a port city in southeastern China: Perspectives from nitrate dual isotopes and NOx emission inventory - Qi-Yu Miao; Xiang Li; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Xi-Jie Yin (Atmospheric Pollution Research, 2025)

Operational parameters regulate in-situ emissions of volatile organic compounds (VOCs) and greenhouse gases (GHGs) during kitchen waste composting: Linking functional microbial dynamics to emission mitigation - Jiayi Zhang; Xiaowen Li; Junsheng Xiong; Hao Mei; Weiqin Zhu; Miaomiao He; Xiaofang Zhang; Ying Ding (Waste Management, 2025)

Molecular dynamics simulation of BS12 and SDS mixed adsorption at the CO2-water interface: Evaluation of interfacial elasticity and permeability - Jingwei Li; Bo Peng; Jiaxin Xiong; Dan Luo; Xiaofeng Li; Jixiang He; Hongfeng Zhang (Fuel, 2025)

Identification of novel antioxidant peptides from cottonseed meal co-fermented with Lactobacillus mucosae LLK-XR1 and acid proteases: In silico screening, molecular simulation, and in vitro functional analysis - Liangkang Lv; Qingqing Lv; Yang Yang; Fengliang Xiong; Shiteng Pei; Shanshan He; Baiou Li; Lijian Wu; Zhijun Cao; Shengli Li; Hongjian Yang (Food Chemistry, 2025)

Diazotrophic community difference between specialists and generalists in response to arsenic and antimony contaminations - Yan Wang; Yiqun Xiong; Yongbin Li; Liu He; Mingyue Chen; Rongbin Fu; Yu Xiao (Environmental Research, 2025)

Surface-enhanced fluorescence-encoded nanoprobes for contrast-enhanced single-cell imaging of gene expression - Lulu Song; Shuang Li; Chaojie Su; Ya Wang; Yifu Wang; Yiqiong Hu; Yamin Xiong; Leiliang He (Chemical Engineering Journal, 2025)

Porous poly (lactic-co-glycolic acid) microspheres loaded with neutral and acidic ginseng polysaccharides ameliorate pneumonia in mice - Wenfei Lan; Li Tao; Kaixuan Mao; Shixin Song; He Liu; Yanru Li; Xiaotong Wang; Lei Yu; Boyu Xiong (Carbohydrate Polymers, 2025)

Will benefits of physical activity in reducing the risk of all-cause and cause-specific mortality be attenuated by exposure to air pollutant mixture? A prospective study in the UK Biobank - Hao Fu; Haijuan Xiong; Hao Bai; Yuanliang He; Zhaohui Zhang; Jianhao Xu; Jiayu Li; Fan He; Mengling Tang; Jianbing Wang; Kun Chen; Mingjuan Jin (Atmospheric Environment, 2025)

Efficient Adsorption of Dye Pollutant by Anchoring Zr-MOF@GO Composite Matrix Microspheres: Performance and Mechanism Insights - Qianhui Ou; Yan Xiong; Li Chen; Deyong He; Chuxiang Zhou; Lan Wang (Water, Air, & Soil Pollution, 2025)

Annual winter wheat mapping for unveiling spatiotemporal patterns in China with a knowledge-guided approach and multi-source datasets - Gaoxiang Yang; Xingrong Li; Yuan Xiong; Meng He; Lei Zhang; Chongya Jiang; Xia Yao; Yan Zhu; Weixing Cao; Tao Cheng (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Enhancing food security and farmers’ profit through ratoon rice-potato rotation in central China - Longxin He; Bin Du; Li Xiong; Ping Wang; Wenxue Zhang; Muhammad Imran; Gang Sun; Fusheng Yuan; Zengbing Liu; Xiong Yao (European Journal of Agronomy, 2025)

GGT-targeting polysarcosine-decorated CaCO3 nanoplatform for ICD-enhanced breast cancer immunotherapy - Xikuang Yao; Fei Xiong; Haobo Chen; Xudong Cao; Qinyi Chen; Jiayu He; Liyuan Zhang; Weina Zhang; Wenpei Fan; Xin Li; Wei Huang (Chemical Engineering Journal, 2025)

Singlet oxygen-driven selective guanine oxidation in Fenton-like system enables efficient removal of antibiotic resistance genes - Xiaoyu Liu; Bingkun Huang; Ying Li; Zelin Wu; Jing Zhang; Yanbiao Shi; Chuan-Shu He; Jianping Zou; Zhaokun Xiong; Bo Lai (Chemical Engineering Journal, 2025)

Hesperidin-loaded self-assembled supramolecular hydrogel based on quaternized chitosan as efficient photothermal antibacterial dressing for MRSA-infected wound healing - Yamin Xiong; Yi Hao; Linlin Ding; Jinjin Li; Yuan Cao; Shuhui Fan; Fangxia Guan; Leiliang He (Carbohydrate Polymers, 2025)

Synergistic Roles for Highly Efficient Removal of Cr(VI) from Aqueous Solution by Attapulgite-Loaded Sulfidized Nanoscale Zero-Valent Iron - Qi He; Sitian Cai; Yantong Chen; Yang Gao; Rongzhong Wang; Huixin Xiong; Jian Li; Yiqun Xu; Wenjing Xue (Water, Air, & Soil Pollution, 2025)

Grazing overrides precipitation reduction to regulate growth of a dominant species in a typical steppe - Liyuan Shi; Zhen Wang; Xiong Z. He; Lan Li; An Hu; Fujiang Hou (Agriculture, Ecosystems & Environment, 2025)

Eco-friendly waterborne SrAl2O4:Eu2+, Dy3+ luminous road markings: Preparation method with enhanced durability - Yinzhang He; Kun Xiong; Rui Li; Ling Wang; Xiaokang Zhao; Lei Shao; Jiupeng Zhang; Jianzhong Pei (Transportation Research Part D: Transport and Environment, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Mechanical synthesis of novel composite ZIF-8/BiOBr to promote interfacial charge transfer for broad application to organic pollutants: Batch experiments and theoretical calculations - Shuangqin Tian; Shujie Wang; Yi He; Bifang Zheng; Huan Xiong; Li Li; Yongtao Wang; Lihong Tang (Journal of Environmental Chemical Engineering, 2025)

Enhanced transformation of sulfadiazine by horseradish peroxidase activated persulfate progress: Characteristics, pathways, mechanisms, and ecotoxicities - Yifei Leng; Ying Zhang; Xiong Chen; Ting He; Fengyi Chang; Zhu Li; Yu Huang; Jun Wang; Wen Xiong (Journal of Environmental Chemical Engineering, 2025)

Chemical composition, antioxidant activity, α-glucosidase inhibitory activity, and metabolomic profiling of Dendrobium officinale across diverse growing regions and cultivation modes - Shu He; Zhengli Lu; Rurui Li; Chun Chen; Xiong Fu; Kin Weng Kong; Amin Ismail; Xuechun Zhang; Zhenxing Wang (Food Bioscience, 2025)

On the assessment of dynamic thermal comfort and pedestrian psychophysiological responses during heatwaves: A focused analysis - Mengyuan He; Hong Liu; Fengwei Xiong; Zhaosong Fang; Xiwen Feng; Baizhan Li; Risto Kosonen (Building and Environment, 2025)

Sex-Specific Association Between Urinary Metal and Serum Homocysteine Levels in Chinese Older Adults: A Study Based on the Yinchuan Community-Dwelling Elderly Cohort - Zhongyuan Zhang; Kai Wang; Siyu Duan; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Pei He; Rui Wang; ZeYang Bai; JinHao Jia; Limeng Xiong; Xiaoyu Li; et al. (Exposure and Health, 2025)

Terrimonas alba sp. nov., an Ochratoxin A-Degrading Strain Isolated from Lakeside Soil - Miaohuan Xiong; Huipeng Wu; Jialu Li; Yingying Wan; Xuelan Chen; Bin Liu; Jian He (Current Microbiology, 2025)

Health risk assessment of heavy metal emissions from on-road vehicles in a metropolitan area in southeastern China - Qi-Yu Miao; Zhe-Nan Wen; Shui-Ping Wu; Jun Hu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu (Journal of Atmospheric Chemistry, 2025)

Role of organophosphorus pesticides in facilitating plasmid-mediated conjugative transfer: Efficiency and mechanisms - Zhixiang Xu; Siyuan Li; Yitao Ma; Caiqing Li; Hao Lu; Jinrui Xiong; Guangzhou He; Ruiying Li; Xiaomin Ren; Bin Huang; Xuejun Pan (Journal of Hazardous Materials, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Association of pentachlorophenol in urine and follicular fluid with ovarian reserve and reproductive outcomes among women undergoing in vitro fertilization based on a prospective cohort study - Li Luo; Xi Qian; Yalin Duan; Xiao Luo; Ruijia Li; Xiaodong Zhang; Xiaoni Guo; Shun Xiong; Guoning Huang; Huaicai Zeng; Qi Zhang; Yanjian Wan; et al. (Environmental Research, 2025)

Enhanced iodinated disinfection byproducts formation in iodide/iodate-containing water undergoing UV-chloramine sequential disinfection: Machine learning-aided identification of reaction mechanisms - Zhen-Ning Luo; Huan He; Tian-Yang Zhang; Xiu-Li Wei; Zheng-Yu Dong; Meng-Yuan Xu; Heng-Xuan Zhao; Zheng-Xiong Zheng; Ren-Jie Pan; Chen-Yan Hu; Chao Zeng; Mohamed Gamal El-Din; et al. (Water Research, 2025)

Proteomic insight into growth and defense strategies under low ultraviolet-B acclimation in the cyanobacterium Nostoc sphaeroides - Zhen Chen; Xun Wu; Zhe Liu; Zhen He; Hua-Hua Yue; Fei-Fei Li; Kui Xu; Hai-Chen Shao; Wei-Zhi Li; Xiong-Wen Chen (Journal of Photochemistry and Photobiology B: Biology, 2025)

Reducing wastewater toxicity to mammalian cells by recycling ferrate(VI) flocs: Roles of flocculation and ferrate(VI) activation - Ye Du; Jie Li; Zhongjuan Wang; Yang Liu; Chuanshu He; Zhaokun Xiong; Bo Lai (Journal of Cleaner Production, 2025)

Aeration strategies for microalgae in wastewater treatment: Enhancing pollutant removal and community dynamics - Pan Li; Yajun Luo; Fei Ming; Jingxian Zheng; Zhicheng Pan; Rui Wang; Yanqing He; Miao Zhou; Xin Xiong; Chi Zhang; Yu Lei; Zhaoqi Wang; et al. (Journal of Environmental Management, 2025)

A convenient double defect engineering avenue for NH2-MIL-125 to enhance photocatalytic hydrogen evolution and NO removal via accelerating the electron mobility - Xingyan Liu; Tianrong Xiong; Yonggang Xu; Kunhe Yang; Youzhou He; Haifeng Yang; Hong Wu; Jiajia Jing; Siqi Li; Siping Wei (Fuel, 2025)

Legacy effects of grazing and nitrogen fertilization on soil carbon, nitrogen and phosphorus in an alpine meadow on the Qinghai-Tibetan Plateau - Lan Li; Xiong Zhao He; Yi Sun; Tianhao Xiao; Yang Liu; Fujiang Hou (European Journal of Soil Biology, 2025)

Revealing the synergistic impacts of ZIF-8 and copper co-exposure on zebrafish behavior, tissue damage, and intestine microbial community - Wenbin Li; Weiping Xiong; Siying He; Fang Li; Yalin Chen; Zhongwu Li; Zhaohui Yang; Zhuotong Zeng; Biao Song (Environmental Research, 2025)

Keystone bacterial groups dominate Escherichia coli O157:H7 survival in long-term reclaimed water headwater stream - Di Zhu; Zhangheng Feng; Bin He; Jinyi Li; David Z. Zhu; Jinbo Xiong; Zhiyuan Yao (Environmental Pollution, 2025)

Exosomes derived from follicular fluid promote proliferation and suppress apoptosis of yak (Bos grunniens) granulosa cells by enhancing antioxidant capacity in vitro - Bangting Pan; Xupeng Li; Qinhui Yang; Yumian Xie; Zhuo Chen; Jun Yu; Honghong He; Yan Xiong; Wei Fu; Shi Yin; Daoliang Lan; Jian Li; et al. (Animal Reproduction Science, 2025)

Different wetting states in riparian sediment ecosystems: Response to microplastics exposure - Siying He; Yuhang Ye; Yajing Cui; Xiuqin Huo; Maocai Shen; Fang Li; Zhaohui Yang; Guangming Zeng; Weiping Xiong (Water Research, 2025)

Impact of road infrastructure on wildlife corridors in Hainan rainforests - Guoling Xiong; Fan Yang; Tongli Wang; Rongxiao He; Lanxi Li (Transportation Research Part D: Transport and Environment, 2025)

Residential VOC from building materials: Exposures, health risks, and ambient hazards - Yi Fan; Chanchan Hu; Zhaokun Wang; Haimei Wang; Ruosu Zhang; Dongxia Jiang; Xueqiong He; Linyan Li; Jack M. Wolfson; Jianyin Xiong; Shaodan Huang; Yinping Zhang; et al. (Sustainable Cities and Society, 2025)

A post-modified lanthanide metal-organic frameworks as ratiometric luminescent sensor for the visual detection of 5-hydroxytryptamine - Congmin Sun; Xiao Liu; Huimin Zhuo; Xu He; Zerong Ge; Ying Zhang; Zhiqiang Li; Qingqing Xiong (Journal of Hazardous Materials, 2025)

Non-additive effects of leaf-litter flammability on eight subtropical tree species: Implications for forest species composition and fire susceptibility - Pujie Wei; Li Tang; Zixuan Xiong; Byron B. Lamont; Lin Chen; Weixing Xue; Zeyao Zhao; Wenxiong Lu; Jisi Han; Wanwan He; Wei Yang; Zhaogui Yan (Journal of Environmental Management, 2025)

Impact of water diversion practices on spatiotemporal changes in hydrologic and hydrochemical landscapes of surface and groundwater - Ling Xiong; Ala Aldahan; Peng He; Xiang Lu; Yuan Ji; Peng Yi; Kai Li; Xuegao Chen (CATENA, 2025)

Design, synthesis and biological evaluation of 5H-[1,2,4]triazino[5,6-b]indole derivatives bearing a pyridinocycloalkyl moiety as iron chelators - He Li; Yali Gao; Xin Ni; Yizu Xiong; Peixi Zhang; Han Liu; Xingye Wu; Dandan Tong; Cuifang Wang; Junjie Ma (Molecular Diversity, 2025)

Mitochondria-targeted antioxidant MitoQ improves the quality of low temperature-preserved yak semen via alleviating oxidative stress - Yanjin Zhu; Jun Yu; Qinhui Yang; Yumian Xie; Xupeng Li; Zhuo Chen; Yan Xiong; Wei Fu; Honghong He; Shi Yin; Daoliang Lan; Jian Li; et al. (Animal Reproduction Science, 2025)

Molecular characterization of MSX2 gene and its role in regulating steroidogenesis in yak (Bos grunniens) cumulus granulosa cells - Jun Ma; Gan Yang; Xuan Qin; Luoyu Mo; Xianrong Xiong; Yan Xiong; Honghong He; Daoliang Lan; Wei Fu; Jian Li; Shi Yin (Theriogenology, 2025)

SLC40A1+ macrophages contribute to the immunosuppressive tumor microenvironment in EGFR-mutated lung cancer - Xinyu Song; Zongjuan Li; Xuanhe Wang; He Du; Yijun Jia; Shen Chen; Anwen Xiong; Wei Li; Xuefei Li; Lei Cheng; Chao Zhao; Lei Wang; et al. (Science Bulletin, 2025)

Deposition history of polycyclic aromatic hydrocarbons in tibetan lakes indicate the effectiveness of protected area establishment - Songhan Li; Xiyu Ban; He Zhang; Yaxin Xiong; Jun Li; Guo-Li Yuan (Journal of Environmental Management, 2025)

Exploring micro(nano)plastics toxicity from an environmental management perspective: Zebrafish as a vital bridge for assessing potential human health risks - Wenbin Li; Biao Song; Zhuotong Zeng; Zhaohui Yang; Fang Li; Siying He; Jing Tong; Yalin Chen; Chang Zhang; Dongbo Wang; Zhongwu Li; Weiping Xiong (Journal of Environmental Management, 2025)

Microplastics enhance the adsorption capacity of zinc oxide nanoparticles: Interactive mechanisms and influence factors - Weiping Xiong; Min Hu; Siying He; Yuhang Ye; Yinping Xiang; Haihao Peng; Zhaomeng Chen; Zhengyong Xu; Honglin Zhang; Weixiang Li; Shudian Peng (Journal of Environmental Sciences, 2025)

Molybdenum disulfide regulates antibiotic resistance gene conjugative transfer under different light conditions: Oxidative stress and antioxidant response - Zhixiang Xu; Yitao Ma; Siyuan Li; Hao Lu; Caiqing Li; Jinrui Xiong; Longlong Miao; Guangzhou He; Keying Chen; Bin Huang; Xuejun Pan (Chemical Engineering Journal, 2025)

Pseudohalogen regulation of benzimidazole small molecule acceptor to optimize molecular crystallinity in Q-PHJ organic solar cells - Zihao Deng; Waqar Ali Memon; Hanjian Lai; Yongmin Luo; Heng Li; Yunpeng Wang; Shilong Xiong; Jiaying Wu; Feng He (Chemical Engineering Journal, 2025)

Comparing the improvement of occupant thermal comfort with local heating devices in cold environments - Xueyue Zhu; Hong Liu; Mengyuan He; Yuxin Wu; Fengwei Xiong; Baizhan Li (Building and Environment, 2025)

Spatiotemporal distribution patterns of large and medium-sized mammals in a biodiversity hotspot: mplications for conservation - Wenqiang Hu; Xueyou Li; Kenneth Otieno Onditi; Hongjiao Wang; Wenyu Song; Zhechang Hu; Changzhe Pu; Mingjing Pu; Yun Xiong; Suhua Yang; Lin Zhu; Jianqiang Yin; et al. (Biological Conservation, 2025)

Heavy metal emissions from on-road vehicles in Xia-Zhang-Quan metropolitan area in southeastern China from 2015 to 2060: impact of vehicle electrification - Zhe-Nan Wen; Qi-Yu Miao; Jiang-Ru Chen; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Zhi Huang (Environmental Science and Pollution Research, 2024)

Mosaicking and Correction Method of Gaofen-3 ScanSAR Images in Coastal Areas with Subswath Overlap Range Constraints - Jiajun Wang; Guowang Jin; Xin Xiong; Jiahao Li; Hao Ye; He Yang (Journal of Marine Science and Engineering, 2024)
The ScanSAR mode image obtained by the Gaofen-3 (GF-3) satellite has an imaging width of up to 130–500 km, which is of great significance in monitoring oceanography, meteorology, water conservancy, and transportation. To address the issues of subswath misalignment and the inability to correct in the processing of GF-3 ScanSAR images in coastal areas using software such as PIE, ENVI, and SNAP, a method for mosaicking and correcting GF-3 ScanSAR images with subswaths that overlap within specified range constraints is proposed. This method involves correlating the coefficients of each subswath thumbnail image in order to determine the extent of the overlap range. Given that the matching points are constrained to the overlap between subswaths, the normalized cross-correlation (NCC) matching algorithm is utilized to calculate the matching points between subswaths. Subsequently, the random sampling consistency (RANSAC) algorithm is employed to eliminate the mismatching points. Subsequently, the subswaths should be mosaicked together with the stitching translation of subswaths, based on the coordinates of the matching points. The image brightness correction coefficient is calculated based on the average grayscale value of pixels in the overlapping region. This is performed in order to correct the grayscale values of adjacent subswaths and thereby reducing the brightness difference at the junction of subswaths. The entire ScanSAR slant range image is produced. By employing the Range–Doppler model for indirect orthorectification, corrected images with geographic information are generated. The experiment utilized three coastal GF-3 ScanSAR images for mosaicking and correction, and the results were contrasted with those attained through PIE software V7.0 processing. This was conducted to substantiate the efficacy and precision of the methodology for mosaicking and correcting coastal GF-3 ScanSAR images.

Winter wheat mapping without ground labels via automated knowledge transfer across regions and years - Gaoxiang Yang; Xingrong Li; Yuan Xiong; Meng He; Xue Wang; Xia Yao; Yan Zhu; Weixing Cao; Tao Cheng (Computers and Electronics in Agriculture, 2024)

Plant diversity value of informal green spaces in tropical coastal urban areas: An empirical study of species, functional, and phylogenetic diversity - Rongxiao He; Lanxi Li; Guangyu Wang; Lingyi Cao; Guoling Xiong; Fan Yang (Science of The Total Environment, 2024)

Exploring stem cell technology: Pioneering new pathways for female fertility preservation and restoration - Ningjing Li; Xinrong Du; Yuhong Zhao; Qin Zeng; Changli Han; Dongsheng Xiong; Libing He; Guohui Zhang; Weixin Liu (Reproductive Biology, 2024)

Mechanisms of radical regulation during carbamazepine degradation by UV-LED/chlorine process with different wavelengths in water - Qi Fu; Zhi Zhang; Yi-Li Lin; Tian-Yang Zhang; Yun-Lu Zhang; Renjie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Jian Lu; Zheng-Ning Luo; Chao Zeng; Huan He; et al. (Journal of Environmental Chemical Engineering, 2024)

Enhanced Fenton degradation of methylene blue dye using CuFe2O4/Fe2O3/CHCP heterogeneous catalyst for superior H2O2 activation - Vasanthakumar Vasudevan; Baoyou Pei; Wentao Xiong; Jiao He; Shixuan Li; Dongha Huang; Xu Liao; Jinqing Lin (Journal of Environmental Chemical Engineering, 2024)

Enhancement of cold-adapted heterotrophic nitrification and denitrification in Pseudomonas sp. NY1 by cupric ions: Performance and mechanism - Lu Yang; Tengxia He; Yulan Yuan; Yufen Xiong; Hongxue Lei; Manman Zhang; Mengping Chen; Li Yang; Chunxia Zheng; Cerong Wang (Bioresource Technology, 2024)

Bioinformatics Analysis and Experimental Validation of Differential Genes and Pathways in Bone Nonunions - Wei Xiong; Xing-Li Shu; Lv Huang; Su-Qi He; Lang-Hui Liu; Song Li; Zi-Chen Shao; Jun Wang; Ling Cheng (Biochemical Genetics, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

A frictional arch model for pile-cap-beam-supported embankment - Guowei Li; Li Xiong; Yang Zhou; Guanjun He; Guangyu Liu; Xinrong He (Transportation Geotechnics, 2024)

Integrative analysis of transcriptome and metabolome reveals the heterogeneity of ovarian follicles between high-altitude Yak (Bos grunniens) and Low-altitude cattle (Bos taurus) - Hongmei Xu; Zifeng Ma; Jinlun Lu; Yueyue Li; Qiao Li; Shi Yin; Honghong He; Yan Xiong; Xianrong Xiong; Jian Li; Daoliang Lan; Wei Fu (Livestock Science, 2024)

Toward separation and purification of chlorogenic acid from Lonicerae Japonicae Flo (honeysuckle) using melamine–formaldehyde aerogel: A green and efficient approach - Yong Zhu; Bingmin Wu; Songyan Xia; Guangzhen Zheng; Juanjuan Cheng; Song Huang; Qingping Xiong; Jing Chen; Hailun Li; Hajime Hirao; Yisheng He; Jihang Chen (Chemical Engineering Journal, 2024)

Robust polymer electrolytes with fast ion-transport nanochannels constructed by carbon dots for long lifespan Li metal batteries - Jia-Wen Ni; Xi-Rong Zhang; Tian-Bing Song; Zun-Hui Huang; Qian-Li Ma; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2024)

Oral Microbiota and Porphyromonas gingivalis Kgp Genotypes Altered in Parkinson’s Disease with Mild Cognitive Impairment - Dongcheng Li; Tengzhu Ren; Hao Li; Mingdi Huang; Jiaxin Chen; Qishan He; Wei Lv; Hailing Liu; Renshi Xu; Xiong Zhang (Molecular Neurobiology, 2024)

Degradation of UV328 by ozone/peroxymonosulfate system: Performance and mechanisms - Mengyu Wang; Can He; Zhongguo Zhang; Chenfei Zhang; Huiqin Xiong; Xin Xie; Cheng Zhu; Yuanmin Xu; Jiuyi Li (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

In-situ assembly of polypyrrole onto heterocyclic aramid for high-strength, ultratough, durable, and multifunctional films - Jinhua Xiong; Xu Zhao; Pengyang Li; Huanxin Lian; Qian Yan; He Chen; Zonglin Liu; Zhong Chen; Qingyu Peng; Xiaodong He (Chemical Engineering Journal, 2024)

Engineering highly efficient root-inspired microporous layer for high-performance fuel cells - Qinglin Wen; Can He; Fandi Ning; Min Shen; Yiyang Liu; Zhi Chai; Xi Cheng; Xiong Dan; Siyi Zou; Wei Li; Lei He; Bin Tian; et al. (Chemical Engineering Journal, 2024)

Optimizing growth and antioxidant function in heat-stressed broilers with vitamin C and betaine supplementation - Yan Li; Junjun Yuan; Shiang Sun; Feiyang Ma; Yongjie Xiong; Shaojun He (International Journal of Biometeorology, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Development path for China's mega-large urban agglomerations based on the water-energy-food nexus - Wei Li; Jianhua Wang; Yong Zhao; Shan Jiang; Yongnan Zhu; Tianxin Qi; Minhua Ling; Justin S. Baker; Yiying Xiong; Fan He; Haihong Li; Guohua He; et al. (Journal of Cleaner Production, 2024)

Concurrent and legacy effects of sheep trampling on soil organic carbon stocks in a typical steppe, China - Lan Li; Xiong Zhao He; Jing Zhang; Racheal Bryant; An Hu; Fujiang Hou (Journal of Environmental Management, 2024)

Targeting the Ferroptosis and Endoplasmic Reticulum Stress Signaling Pathways by CBX7 in Myocardial Ischemia/reperfusion Injury - Weipeng Jiang; Zeyu Yan; Xueou Zheng; Shiyi Huang; Yue Hu; Fengjuan Xiong; Bufan He; Yingzhi Wu; Qiang Fu; Zhiliang Li; Baihua Zhou (Cell Biochemistry and Biophysics, 2024)

Prediction of g–C3N4–based photocatalysts in tetracycline degradation based on machine learning - Chenyu Song; Yintao Shi; Meng Li; Yuanyuan He; Xiaorong Xiong; Huiyuan Deng; Dongsheng Xia (Chemosphere, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Influence of sorbitol as a green and inexpensive corrosion inhibitor for Al-air batteries: An experimental and theoretical study - Lili Li; Yiwen Zhu; Liping Xiong; Zhongyi He; Yaoxuan Zhang (Chemical Engineering Journal, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Long-term polystyrene nanoparticles exposure reduces electroretinal responses and exacerbates retinal degeneration induced by light exposure - Jincan He; Shiyi Xiong; Wenchuan Zhou; Hao Qiu; Yuqing Rao; Ya Liu; Guiyan Shen; Peiquan Zhao; Guangquan Chen; Jing Li (Journal of Hazardous Materials, 2024)

Evaluating the impact and heterogeneity of China's OFDI on total-factor carbon emission performance in Belt and Road Initiative countries - Pin Li; Qi He; Jinsuo Zhang; Jing Xiong (Journal of Cleaner Production, 2024)

Micro-helical Ni3Fe chain encapsulated in ultralight MXene/C aerogel to realize multi-functionality: Radar stealth, thermal insulation, fire resistance, and mechanical properties - Sen Lin; Jing Lin; Zhiqiang Xiong; Xue He; Xin Li; Chongbo Liu; Chengying Wang; Xiaojun Zeng; Xuliang Nie; Renchao Che (Chemical Engineering Journal, 2024)

Creatine kinase elevation in chronic hepatitis B patients with telbivudine therapy: influence of telbivudine plasma concentration and single nucleotide polymorphisms of TK2, RRM2B, and NME4 - Tianye He; Bicui Chen; Yaqun Li; Yun Song; Jian Wu; Biyu Xiong; Bin Wang; Jianfei Long (European Journal of Clinical Pharmacology, 2024)

Functional comparison of Rab3aa and Rab3ab in grass carp (Ctenopharyngodon idella) immune response and GCRV replication - Lifei Luo; Lv Xiong; Cheng Yang; Libo He; Lanjie Liao; Yongming Li; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Administration of Arginine Vasotocin and modified Isotocin improve artificial propagation and post-spawning survival of female yellow catfish - Yang Xiong; Xu Wang; Ruidong Sun; Youbo Jiang; Zhipeng He; Jian Chen; Pei Li; Jie Mei (Aquaculture, 2024)

High-valent metal-oxo species transformation and regulation by co-existing chloride: Reaction pathways and impacts on the generation of chlorinated by-products - Hongyu Zhou; Yong-li He; Jiali Peng; Xiaoguang Duan; Xiaohui Lu; Heng Zhang; Yang Liu; Chuan-shu He; Zhaokun Xiong; Tianyi Ma; Shaobin Wang; Bo Lai (Water Research, 2024)

Effects of exogenous application of the strigolactone GR24 on quality and flavor components during postharvest storage of celery - Mengyao Li; Xiaoyan Li; Jiageng Du; Weilong Li; Ruiyuan He; Yuanxiu Lin; Yunting Zhang; Yan Wang; Wen He; Qing Chen; Yong Zhang; Xiaorong Wang; et al. (Postharvest Biology and Technology, 2024)

Covalent copper-organic frameworks with light-activable catalytic centers as smart artificial enzymes for highly sensitive and wide-range biocatalytic diagnosis - Chao Xiong; Qian Li; Jiani Yang; Liang Cheng; Mohsen Adeli; Xianglin Luo; Xiaohui Xu; Chao He; Chong Cheng (Chemical Engineering Journal, 2024)

The novel probiotic preparation based on Lactobacillus spp. mixture on the intestinal bacterial community structure of Cherry Valley duck - Shuiqin Shi; Mengrui Ge; Yan Xiong; Yixun Zhang; Wenhui Li; Zhimuzi Liu; Jianfen Wang; Enhui He; Liming Wang; Duoqi Zhou (World Journal of Microbiology and Biotechnology, 2024)

Genetic dissection of Brassica napus seed vigor after aging - Yiran Ding; Dalin Hou; Yongtai Yin; Kang Chen; Jianjie He; Shuxiang Yan; Huaixin Li; Yiyi Xiong; Weixian Zhou; Maoteng Li (Theoretical and Applied Genetics, 2024)

Robustness of design flood estimates under nonstationary conditions: parameter sensitivity perspective - Bin Xiong; Shuchen Zheng; Qiumei Ma; Chun Fu; Tianfu Wen; Zhongzheng He; Lingqi Li; Chong-Yu Xu (Stochastic Environmental Research and Risk Assessment, 2024)
The changing frequency of flooding in global watersheds, driven by various human and natural factors like land use/cover changes and global warming, necessitates innovative approaches in flood frequency analysis and risk assessment. Nonetheless, the reliability of nonstationary frequency analysis models remains a concern given challenges in accurately measuring the uncertainty introduced by these methods and the impact on design flood values. In this study, deviation-based differential sensitivity indices, including single-parameter (SDDSI) and entire-parameter (EDDSI) measures were developed to assess the influence of parameter uncertainty in nonstationary models using Bayesian statistics and "equivalent reliability" nonstationary design. The Weihe River, the largest tributary of the Yellow River which is experiencing both climate change and heavy impact of human activities, is chosen to be the study area to investigate the impact of precipitation change and land use change on nonstationary flood frequency. Results show that in the One-At-A-Time (OAT) sensitivity analysis under a small uncertainty scenario (SUS) for parameter inputs, the shape parameter stands out as the most influential factor (SDDSI_SUS = 0.347) affecting the 100-year design flood in the Stationary Generalized Extreme Value (SGEV) model. For the Non-Stationary GEV (NGEV) models, the influence of this parameter is less pronounced, with SDDSI_SUS values of 0.095 and 0.093 for the SSP126 and SSP585 scenarios, respectively. Instead, attention turns to the regression coefficient of the grassland area, associated with the GEV scale parameter. In global sensitivity analysis under the posterior uncertainty scenario (PUS) for parameter inputs, the EDDSI_PUS values for SGEV, NGEV_SSP126, and NGEV_SSP585 models were 0.52, 1.41, and 1.30, respectively, inferring heightened sensitivity of NGEV models to perturbations from entire parameters. It is anticipated that incorporating additional evidence, such as historical flood data, is essential for accurate nonstationary hydrological design to mitigating the influence of parameter uncertainty. The sensitivity indices in this study provide significant insights for assessing the robustness of nonstationary hydrological design in flood risk management and applications.

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Recombinant Bacillus subtilis expressing functional peptide and its effect on the growth, antioxidant capacity and intestine in Megalobrama amblycephala - Wei Xiong; Xiufei Cao; Keke Chen; Chaofan He; Xi Wang; Huixing Guo; Haokun Hua; Xiaoe Xiang; Xiaoyu Chu; Yanzou Dong; Wenbin Liu; Xiangfei Li; et al. (Aquaculture, 2024)

Development and assessment of sustainable steel-concrete composite beams with novel demountable shear connections - Liquan Xiong; Song Li; Kaiyu Jiang; Jian He; Fantao Kong (Soil Dynamics and Earthquake Engineering, 2024)

Role of adhesion molecules in cancer and targeted therapy - Chunmei Fan; Fang Xiong; Shanshan Zhang; Zhaojian Gong; Qianjin Liao; Guiyuan Li; Can Guo; Wei Xiong; He Huang; Zhaoyang Zeng (Science China Life Sciences, 2024)

Development of a stable genetic transformation system in Erigeron breviscapus: a case study with EbYUC2 in relation to leaf number and flowering time - Qin Zhu; Ying-Chun Lu; Jing-Lei Xiong; Yun-Hui Yang; Jian-Li Yang; Sheng-Chao Yang; Guang-Hui Zhang; Ben-Cai Sha; Si-Mei He (Planta, 2024)

Reconstructive interpolation for pulse wave estimation to improve local PWV measurement of carotid artery - Ouyang Gu; Bingbing He; Li Xiong; Yufeng Zhang; Zhiyao Li; Xun Lang (Medical & Biological Engineering & Computing, 2024)

A stabilized two-phase material point method for hydromechanically coupled large deformation problems - Xiong Tang; Xinpo Li; Siming He (Bulletin of Engineering Geology and the Environment, 2024)

GBM-ILM: Grey-Box Modeling Based on Incremental Learning and Mechanism for Unmanned Surface Vehicles - Mengwei Zhang; Decai Li; Junfeng Xiong; Yuqing He (Journal of Marine Science and Engineering, 2024)
Unmanned surface vehicles (USVs) have garnered significant attention across various application fields. A sufficiently accurate kinetic model is essential for achieving high-performance navigation and control of USVs. However, time-varying unobservable internal states and external disturbances pose challenges in accurately modeling the USV’s kinetics, and existing methods face difficulties in accurately estimating unknown time-varying disturbances online while ensuring precise mechanism modeling. To address this issue, a novel grey-box modeling method based on incremental learning and mechanisms (GBM-ILM) is proposed. Its union structure combines the advantages of both incremental learning networks and physical mechanisms for estimating the USV’s full kinetics. Depending on the linear parameter-varying (LPV) mechanism, it not only adheres to physical laws but also calculates the unstructured model errors. An incremental learning network is implemented to continuously refine model errors, by accounting for the USV’s time-varying characteristics and iteratively updating the network parameters and structures to adapt to different USV states and environmental disturbances. To validate this method, we developed the ‘Salmon’ USV and conducted identification experiments in a lake. Compared to tests of other state-of-the-art methods, our method has better adaptability, with 46.34%, 14.86%, and 6.87% accuracy improvements when estimating the USV’s forward, turning, and sideslip dynamic model, respectively.

Study on the constraint handling method for high-dimensional optimization of cascade reservoirs - Shuliang Li; Zhongzheng He; Wei Huang; Bowen Wei; Feng Yan; Jisi Fu; Bin Xiong (Journal of Cleaner Production, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Multifunctional tension–compression conversion sensing structure inspired by rotating stairs - Pengyang Li; Xu Zhao; Qian Yan; Jinhua Xiong; Renjie Ding; Haowen Zheng; Fuhua Xue; Zhong Chen; Zonglin Liu; He Chen; Zhigong Tang; Qingyu Peng; et al. (Chemical Engineering Journal, 2024)

Maternal exposure to polystyrene nanoplastics causes defective retinal development and function in progeny mice by disturbing metabolic profiles - Shiyi Xiong; Jincan He; Hao Qiu; Cornelis A.M. van Gestel; ErKai He; Zhengdong Qiao; Liang Cao; Jing Li; Guangquan Chen (Chemosphere, 2024)

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

In vitro digestion and fecal fermentation of encapsulated starch constructed via layer-by-layer coating of calcium alginate - Congli Cui; Mingju Li; Xiaoyang He; Na Ji; Yang Qin; Lei Dai; Liu Xiong; Qingjie Sun (Food Hydrocolloids, 2024)

An improved constrained velocity inversion algorithm for geological structures - Jing-Xuan Xiong; Zhen-Hua He; Le Li; Guamg-Ming He; Hong Liu; Lian-Jun Li; Guang-Yin Wang; En-Jia Zhang (Applied Geophysics, 2024)

Comparison of leaf chlorophyll content retrieval performance of citrus using FOD and CWT methods with field-based full-spectrum hyperspectral reflectance data - Bin Xiao; Sunzhe Li; Shiqing Dou; Hongchang He; Bolin Fu; Tengxu Zhang; Weiwei Sun; Yanli Yang; Yuankang Xiong; Jinke Shi; Jie Zhang (Computers and Electronics in Agriculture, 2024)

Grazing-driven shifts in soil bacterial community structure and function in a typical steppe are mediated by additional N inputs - Lan Li; Xiong Zhao He; Mengyuan Wang; Ling Huang; Zhen Wang; Xiumin Zhang; Junqi Hu; Fujiang Hou (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Liriogerphines E–U, further unique sesquiterpene-alkaloid hybrids from the rare Chinese tulip tree - Yu-Hang He; Hong Xiang; Qi-Xiu Li; Yu-Fei Wu; Ze-Xin Jin; Jin-Feng Hu; Yi-Cheng Mao; Juan Xiong (Phytochemistry, 2024)

New coupling technology of phenols extraction in coal tar and carbon dioxide capture: Modeling, optimization and techno-economic analysis - Yonglin Li; Qian Xiong; Huajie Liu; Wenlong Xiao; Qiuhong Ai; Buning Chen; Yusheng Zhou; He'an Luo (Fuel, 2024)

Super-comminuted dietary fiber from pomelo peel regulates blood lipids and gut microbiota and prevents obesity in high-fat diet-fed mice - Jiachen Zhang; Yuchen Shangguan; Jing Ni; Chuanbo He; Ying Ma; Hejian Xiong; Wenjie Jian; Jian Li (Food Bioscience, 2024)

Association of urinary polycyclic aromatic hydrocarbon metabolites with gestational diabetes mellitus and gestational hypertension among pregnant women in Southwest China: A cross-sectional study - Dengqing Liao; Shimin Xiong; Songlin An; Lin Tao; Lulu Dai; Yingkuan Tian; Wei Chen; Caidie He; Pei Xu; Nian Wu; Xiang Liu; Haonan Zhang; et al. (Environmental Pollution, 2024)

High-efficiency solar-driven water purification enhanced by the in-plane temperature gradient and hydrated ions - Renjie Ding; Jinhua Xiong; Qian Yan; Pengyang Li; Xu Zhao; Zhong Chen; Zonglin Liu; Huanxin Lian; Zhigong Tang; Shanyi Du; Qingyu Peng; Xiaodong He (Chemical Engineering Journal, 2024)

Correction: Investigation of the mixed origins of the MGC-803 cell line reveals that it is a hybrid cell line derived from HeLa - Meimei Yang; Jing He; Sixuan Xia; Yudong Wang; Jun Xiong; Cong Liao; Nan Li; Sanfu Qu; Chao Shen (Human Cell, 2024)

Interseismic kinematics along the Tuolaishan-Lenglongling fault determined by Sentinel-1 InSAR observations - Lijia He; Guangcai Feng; Zhiwei Li; Wenbin Xu; Zhiqiang Xiong; Jihong Liu; Kai Sun; Yuedong Wang; Hua Gao; Xiaoge Liu (Tectonophysics, 2024)

Fluctuating oxygenation and dynamic iron cycling in the late Paleoproterozoic ocean - Xiuqing Yang; Jingwen Mao; Rongxi Li; Fang Huang; Chong He; Chao Zhao; Wei Wei; Guowei Yang; Yijun Xiong; Simon W. Poulton (Earth and Planetary Science Letters, 2024)

Water Resources Allocation in a Transboundary River Based on a Rubinstein Bargaining Model - Jisi Fu; Tianwei Lu; Bin Xu; Jieyu Li; Junwei Zhou; Bin Xiong; Zhongzheng He (Water Resources Management, 2024)

Design a dual-response two-photon fluorescent probe for simultaneous imaging of mitochondrial viscosity and peroxynitrite in a thrombosis model - Miantai Ye; Xiaohui yu; Yan Yuan; Meng He; Junli zhuang; Sizheng Xiong; Jie Li; Yanying Wang; Chunya Li; Xiaoxing Xiong; Hongping Deng (Analytica Chimica Acta, 2024)

Slope stability calculation based on sparrow search algorithm and Monte Carlo simulation - Li He; Yong-ming Zhao; Bruno Njamba; Yi-he Liu; Hai-tao Xiong (Arabian Journal of Geosciences, 2024)

Investigation of the mixed origins of the MGC-803 cell line reveals that it is a hybrid cell line derived from HeLa - Meimei Yang; Jing He; Sixuan Xia; Yudong Wang; Jun Xiong; Cong Liao; Nan Li; Sanfu Qu; Chao Shen (Human Cell, 2023)

Kaempferol and ginsenoside Rg1 ameliorate acute hypobaric hypoxia induced lung injury based on network pharmacology analysis - Na Li; Yuan Cheng; Tao Jin; Lirui Cao; Jieyu Zha; Xiong Zhu; Qing He (Toxicology and Applied Pharmacology, 2023)

Single-step hydrothermal synthesis of biochar from waste industrial hemp stalk core for Pb2+ sorption: Characterization and mechanism studies - Zheren Zhang; Nengsheng Liu; Xiang Li; Yunzhu Wang; Yongkang Xiong; Ruirui Meng; Le Liu; Sufang He (Sustainable Chemistry and Pharmacy, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Constructing electrochemical sensor using molecular-imprinted polysaccharide for rapid identification and determination of l-tryptophan in diet - Yan-Jun Li; Li-Li Yang; Li Ni; Jia-Min Xiong; Jia-Yuan He; Lian-Di Zhou; Ling Luo; Qi-Hui Zhang; Chun-Su Yuan (Food Chemistry, 2023)

Optimization of rice husk ash concrete design towards economic and environmental assessment - Bin Xi; Ning Zhang; Huabo Duan; Jintao He; Guanghan Song; Huanyu Li; Xiong Shi (Environmental Impact Assessment Review, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Carrier-free 5-Fu nanoparticle-mediated domestication therapy for scar treatment: A preclinical and first-in-human study - Peng He; Sha Yi; Jianzhong Zhang; Chengchao Chu; Xuqi Peng; Changhong Li; Xinfei Sun; Yang Zhang; Hongwei Cheng; Xia Xiong; Gang Liu (Chemical Engineering Journal, 2023)

Overview and countermeasures of cancer burden in China - Yian Wang; Qijia Yan; Chunmei Fan; Yongzhen Mo; Yumin Wang; Xiayu Li; Qianjin Liao; Can Guo; Guiyuan Li; Zhaoyang Zeng; Wei Xiong; He Huang (Science China Life Sciences, 2023)

Construction and evaluation of a phospholipid-based phase transition in situ gel system for brexpiprazole - Ran Tao; Li Liu; Yingxin Xiong; Qianyu Zhang; Xiangyu Lv; Linbo He; Fang Ren; Lu Zhou; Baoyan Chen; Kexin Wu; Yan Zhang; Huali Chen (Drug Delivery and Translational Research, 2023)

Influence of Blade Flexibility on the Dynamic Behaviors of Monopile-Supported Offshore Wind Turbines - Yongqing Lai; Wei Li; Ben He; Gen Xiong; Renqiang Xi; Piguang Wang (Journal of Marine Science and Engineering, 2023)
At present, monopile-supported offshore wind turbines (MOWTs) are widely used in offshore wind farms. The influence of blade flexibility on the dynamic behaviors of MOWTs excited by waves and earthquakes was investigated in this study. Numerical analysis models were established for 5 MW and 10 MW MOWTs, incorporating flexible and rigid blade configurations. The modes and natural frequencies of the full system were compared between these two numerical models, and their dynamic responses were evaluated under wave-only and earthquake-only excitations. It was revealed that the influence of blade flexibility on the first- and second-order modes of the system can be neglected. The dynamic response of these MOWTs under wave excitation can be predicted by the rigid blade model, where the maximum relative difference is less than 5%. However, higher-order modes of the system are significantly affected by the blade flexibility. Under high-frequency excitations, these higher-order modes of the system are remarkably stimulated. Additionally, a large relative difference, exceeding 50%, is detected when the rigid blade model is used to predict the seismic response of the two MOWTs. Consequently, the blade flexibility should be adequately modeled when predicting the dynamic response of OWTs.

Prophylactic norepinephrine combined with 6% hydroxyethyl starch (130/0.4) co-load infusion for preventing postspinal anesthesia hypotension during cesarean section: a randomized, controlled, dose-finding trial - Lei Guo; Xiangsheng Xiong; Rui Qin; Zhenzhou Li; Yongqiang Shi; Wei Xue; Ling He; Shuqin Ma; Yi Chen (DARU Journal of Pharmaceutical Sciences, 2023)

High-strength, super-tough, and durable nacre-inspired MXene/heterocyclic aramid nanocomposite films for electromagnetic interference shielding and thermal management - Jinhua Xiong; Renjie Ding; Zonglin Liu; Haowen Zheng; Pengyang Li; Zhong Chen; Qian Yan; Xu Zhao; Fuhua Xue; Qingyu Peng; Xiaodong He (Chemical Engineering Journal, 2023)

Zn anode surface engineering for stable zinc-ion batteries: Carbon dots incorporated mesoporous TiO2 as a coating layer - Tian-Bing Song; Qian-Li Ma; Xi-Rong Zhang; Jia-Wen Ni; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Dynamic model and application analysis of flow field interference between marine risers based on improved shielding effect model - Yongli Hu; Lijie Li; Xiangyin He; Xiong Hu (Ocean Engineering, 2023)

An approach to recognizing the working cycle stage with small sample data for energy conservation - Bin He; Chenyue Zhang; Xiaoyang Cao; Guiqin Li; Xin Xiong (Journal of Cleaner Production, 2023)

Influence of circulation types on temporal and spatial variations of ozone in Beijing - Xiaowan Zhu; Jin Wu; Guiqian Tang; Lin Qiao; Tingting Han; Xiaomei Yin; Xiangxue Liu; Ziming Li; Yajun Xiong; Di He; Zhiqiang Ma (Journal of Environmental Sciences, 2023)

Adsorption behavior of antibiotics with different structures onto vivianite in the presence of dissolved organic matter during the phosphorus recovery process - Wang-Xiao Jia; Wen-Qiang Li; Zhi-Hui Xie; Pu-Can Guo; Zhi-Long Ye; Zhao-Kun Xiong; Chuan-Shu He; Bo Lai (Chemical Engineering Journal, 2023)

Paintable graphene oxide-hybridized soy protein-based biogels for skin radioprotection - Daijun Zhou; Hui Liu; Lu Han; Di Liu; Xiaomei Liu; Qingyan Yan; Dan He; ZhiHui Li; Xiong Lu; Chaoyang Jiang; Dong Li (Chemical Engineering Journal, 2023)

Water-dispersible and stable polydopamine coated cellulose nanocrystal-MXene composites for high transparent, adhesive and conductive hydrogels - Bolin Wan; Nana Liu; Zhen Zhang; Xiong Fang; Yugao Ding; Haosheng Xiang; Yunqing He; Mingxian Liu; Xiaoming Lin; Juntao Tang; Yingzhan Li; Biao Tang; et al. (Carbohydrate Polymers, 2023)

Graphene nano zinc oxide reduces the expression and release of antibiotic resistance-related genes and virulence factors in animal manure - Haibo Zhang; Weikun Guan; Jun Shu; Sen Yu; Yingmin Xiong; Gao Liu; Yuhong Zhong; Jia Chen; Zhigang Zhao; Ning He; Qingfeng Xing; Dongsheng Guo; et al. (Science of The Total Environment, 2023)

Investigation of additive-assisted microbial-induced calcium carbonate precipitation in 3D printed cross fractures - Liang Guo; Min Zhang; Mingwei Liao; Baoquan Wang; Xiaoyu He; Yiqi Peng; Xingzhu Lin; Ni He; Zhuhong Xiong; Han Chen; Yehui Shi; Tong Li (Geomechanics for Energy and the Environment, 2023)

Abiotic transformation of synthetic progestins in representative soil mineral suspensions - Xingjian Yang; Rui Wang; Zhili He; Xiong Dai; Xiuping Jiang; He Liu; Yongtao Li (Journal of Environmental Sciences, 2023)

The protective effect of resveratrol on largemouth bass (Micropterus salmoides) during out-of-season spawning - Liulan Zhao; Chen Xiong; Yi Yang; Zhihong Li; Kuo He; Qiao Liu; Zhi He; Jie Luo; Xin Zhang; Zhiqiong Li; Song Yang (Fish & Shellfish Immunology, 2023)

Reduced adsorption of norfloxacin on UV aging microplastics in anoxic environment - Jing He; Sijia Chen; Yulin Xu; Mengxin Sun; Tingting Yang; Li Liang; Xinyu Xiong (Environmental Science and Pollution Research, 2023)

Peracetic acid activation via the synergic effect of Co and Fe in CoFe-LDH for efficient degradation of pharmaceuticals in hospital wastewater - Zhi-Hui Xie; Chuan-Shu He; Yong-Li He; Shu-Run Yang; Si-Ying Yu; Zhaokun Xiong; Ye Du; Yang Liu; Zhi-Cheng Pan; Gang Yao; Bo Lai (Water Research, 2023)

TMT-based quantitative proteomics analysis reveals the differential proteins between fresh and frozen-thawed sperm of yak (Bos grunniens) - Yilin Fan; Xiaowei Li; Yu Guo; Xiaoqiang He; Yanwen Wang; Dan Zhao; Yan Ma; Xinxin Feng; Jiyue Zhang; Jian Li; Xiangdong Zi; Xianrong Xiong; et al. (Theriogenology, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Effect of dietary supplemental vitamin C and betaine on the growth performance, humoral immunity, immune organ index, and antioxidant status of broilers under heat stress - Shiang Sun; Bing Li; Mingming Wu; Yafei Deng; Jing Li; Yongjie Xiong; Shaojun He (Tropical Animal Health and Production, 2023)

Environmentally-friendly biorecovery of manganese from electrolytic manganese residue using a novel Penicillium oxalicum strain Z6-5-1: Kinetics and mechanism - Shuai Zhao; Bo-Wen Zheng; Yu-Cang Wang; Fei He; Li-Juan Wang; Xiong Lin; Xue-Mei Luo; Jia-Xun Feng (Journal of Hazardous Materials, 2023)

Removal of Bisphenol A via peroxymonosulfate activation over graphite carbon nitride supported NiCx nanoclusters catalyst: Synergistic oxidation of high-valent nickel-oxo species and singlet oxygen - Junjie You; Junyi Li; Heng Zhang; Mengfan Luo; Bo Xing; Yi Ren; Yang Liu; Zhaokun Xiong; Chuanshu He; Bo Lai (Journal of Hazardous Materials, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Substratum virtualization in three-dimensional landslide modeling with the material point method - Shuxi Zhao; Lei Zhu; Wei Liu; Xinpo Li; Siming He; Gianvito Scaringi; Xiong Tang; Yang Liu (Engineering Geology, 2023)

Mental health, health-related quality of life, and lung function after hospital discharge in healthcare workers with severe COVID-19: a cohort study from China - Lijuan Xiong; Qian Li; Xiongjing Cao; Huangguo Xiong; Daquan Meng; Mei Zhou; Yanzhao Zhang; Xinliang He; Yupeng Zhang; Liang Tang; Yang Jin; Jiahong Xia; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Assessment of continuity and efficiency of complemented cropland use in China for the past 20 years: A perspective of cropland abandonment - Hang Chen; Yongzhong Tan; Wu Xiao; Tingting He; Suchen Xu; Fei Meng; Xinhui Li; Wenying Xiong (Journal of Cleaner Production, 2023)

Integrated process for zero discharge of coking wastewater: A hierarchical cycle-based innnovation - Xiong Ke; Tuo Wei; Gengrui Wei; Acong Chen; Xiaoqian Cheng; Zemin Li; Zhi Qin; Zijun Pang; Jiamin Pan; Yao Chen; Cong Wei; Xianghong Guan; et al. (Chemical Engineering Journal, 2023)

Circ_CSPP1 Regulates the Development of Non-small Cell Lung Cancer via the miR-486-3p/BRD9 Axis - Dan Xie; Shuyi Zhang; Xiaocong Jiang; Weizhen Huang; Ying He; Yi Li; Sihan Chen; Hailin Xiong (Biochemical Genetics, 2023)

Numerical Simulation on Sand Production Based on Laboratory Gas Hydrate Production Experiment - Jingsheng Lu; Guangrong Jin; Dongliang Li; Deqing Liang; Yong He; Lingli Shi; Yiqun Zhang; Youming Xiong (Journal of Marine Science and Engineering, 2023)
Gas from natural gas hydrate (NGH) is priced competitively with gas prices. Most marine NGH is stored in low cementing strata, which easily cause sand production problems, restricting the commercial production and environmental safety of NGH’s development. This study applied a numerical simulation on sand production in hydrate-bearing sediments’ (HBS) exploitation. The numerical simulation on sand production was carried out for different productions of laboratory NGH exploitation. The results show radial strain appeared to be deformed away from the wellbore and show radial displacement close to the wellbore during mining. Due to the overburden stress condition, the boundary condition wall was a displace less rigid body. The radial displacement was greatly affected by depressurization, which showed the displacement to the wellbore and sanding. The radial strain was dominant by the shear shrinkage phenomenon in the mechanical model, while the reservoir’s radial displacement was away from the wellbore instead. The balance between the fluid driving force of production rates towards the wellbore and radial displacement drawing away from the wellbore is significant to sand production in HBS. The dominant forces of sanding were different mechanical and hydraulic combinations in three periods of GH production.

Chloroplast–boosted photodynamic therapy for effective drug-resistant bacteria killing and biofilm ablation - Xiaofeng He; Wenjing Guo; Yuxuan Tang; Jianming Xiong; Yuanyuan Li; Rongrong Huang; Wenjun Miao (Journal of Photochemistry and Photobiology B: Biology, 2023)

The profiles of durian (Durio zibethinus Murr.) shell phenolics and their antioxidant effects on H2O2-treated HepG2 cells as well as the metabolites and organ distribution in rats - Yangzheng He; Li Peng; Hua Xiong; Wenqiang Liu; Hua Zhang; Xin Peng; Xuemei Zhu; Fanghua Guo; Yong Sun (Food Research International, 2023)

Mice kidney biometabolic process analysis after cantharidin exposure using widely-targeted metabolomics combined with network pharmacology - Tianmu He; Lijuan Xiong; Yixin Zhang; Rong Yan; Ming Yu; Meichen Liu; Liu Liu; Cancan Duan; Xiaofei Li; Jianyong Zhang (Food and Chemical Toxicology, 2023)

A self-adhesive and low-temperature-tolerant strain sensor based on organohydrogel for extreme ice and snow motion monitoring - Zhongwu Bei; Yangwei Chen; Shixing Li; Zhiqiang Zhu; Jietao Xiong; Rongxiang He; Chao Zhu; Yiping Cao; Zhiyong Qian (Chemical Engineering Journal, 2023)

A mathematical model of critical releasable charge for R290 indoor leakage of split-type household air conditioners - Qian Ning; Guogeng He; Jun Xiong; Mingjing Fan; Xiao Li (Building and Environment, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

Different effects of grazing and nitrogen addition on ecosystem multifunctionality are driven by changes in plant resource stoichiometry in a typical steppe - Lan Li; Xiong Zhao He; Xiumin Zhang; Junqi Hu; Mengyuan Wang; Zhen Wang; Fujiang Hou (Plant and Soil, 2022)

Spinal Cord Mapping of Respiratory Intercostal Motoneurons in Adult Mice - Junhong Zhang; Fenlan Luo; Shuancheng Ren; Yaling Wang; Wu Li; Kan Xu; Ziyi Zheng; Chao He; Jianxia Xia; Wei Xiong; Zhi-An Hu (Neuroscience Bulletin, 2022)

Temperature-dependent development and reproduction of Tarsonemus confusus (Acari: Tarsonemidae): an important pest mite of horticulture - Litao Li; Lichen Yu; Limin He; Xiong Zhao He; Rui Jiao; Changxin Xu (Experimental and Applied Acarology, 2022)

Circular RNA circCCNB1 inhibits the migration and invasion of nasopharyngeal carcinoma through binding and stabilizing TJP1 mRNA - Mengyao Zhao; Yian Wang; Fenghua Tan; Lingyun Liu; Xiangchan Hou; Chunmei Fan; Le Tang; Yongzhen Mo; Yumin Wang; Qijia Yan; Zhaojian Gong; Zheng Li; et al. (Science China Life Sciences, 2022)

Maternal urine phthalate metabolite exposure and miscarriage risk: a nested case–control study of the Zunyi Birth Cohort - Xia Wang; Caidie He; Nian Wu; Yingkuan Tian; Linglu Wang; Juan Liao; Derong Fang; Xiang Liu; Songlin An; Wei Chen; Shimin Xiong; Yijun Liu; et al. (Environmental Science and Pollution Research, 2022)

Characterization of a Hyaluronidase-Producing Bacillus sp. CQMU-D Isolated from Soil - Lu Wang; Qianqian Liu; Rui Hao; Jing Xiong; Junxing Li; Yanan Guo; Lu He; Zeng Tu (Current Microbiology, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Histones of Neutrophil Extracellular Traps Induce CD11b Expression in Brain Pericytes Via Dectin-1 after Traumatic Brain Injury - Yang-Wuyue Liu; Jingyu Zhang; Wanda Bi; Mi Zhou; Jiabo Li; Tiantian Xiong; Nan Yang; Li Zhao; Xing Chen; Yuanguo Zhou; Wenhui He; Teng Yang; et al. (Neuroscience Bulletin, 2022)

Effects of Cerebellar Transcranial Direct Current Stimulation in Patients with Stroke: a Systematic Review - Li Hong-yu; Zhang Zhi-jie; Li Juan; Xiong Ting; He Wei-chun; Zhu Ning (The Cerebellum, 2022)

Exposure characteristics of phthalate metabolites among the Zunyi cohort of pregnant women in Southwest China - Juan Liao; Derong Fang; Yijun Liu; Shimin Xiong; Xia Wang; Yingkuan Tian; Haonan Zhang; Songlin An; Caidie He; Wei Chen; Xiang Liu; Nian Wu; et al. (Environmental Science and Pollution Research, 2022)

Sodium selenite attenuates zearalenone-induced apoptosis through inhibition of endoplasmic reticulum stress in goat trophoblast cells - Yongjie Xiong; Bing Li; Jing Li; Erhui Jin; Shaojun He (BioMetals, 2022)

Particle Design and Inhalation Delivery of Iodine for Upper Respiratory Tract Infection Therapy - Kaikai Zhang; Xiaohong Ren; Jiacai Chen; Caifen Wang; Siyu He; Xiaojin Chen; Ting Xiong; Jiawen Su; Shujun Wang; Weifeng Zhu; Jiwen Zhang; Li Wu (AAPS PharmSciTech, 2022)

Pairwise coarse registration of point clouds by traversing voxel-based 2-plane bases - Yongjian Fu; Zongchun Li; Feng Xiong; Hua He; Wenqi Wang; Yong Deng (International Journal of Remote Sensing, 2022)

Extracellular polymeric substances of acidophilic microorganisms play a crucial role in heavy metal ions adsorption - M. Li; X. Deng; W. Sun; L. Hu; H. Zhong; Z. He; D. Xiong (International Journal of Environmental Science and Technology, 2022)

Experimental investigation of the hydraulic properties of large-scale irregular fractured rock masses in granite fault zones - Liang Guo; Xiaoyu He; Zhuhong Xiong; Han Chen; Jiao Zhu; Mingwei Liao; Hao Guo; Xiaozhao Li; Baoquan Wang; Min Zhang; Lei Xing (Hydrogeology Journal, 2022)

Combined game model and investment decision making of power grid-distributed energy system - Yongxiu He; Wei Xiong; Binyou Yang; Hai-yan Yang; Jiu-fang Zhou; Ming-li Cui; Yan Li (Environment, Development and Sustainability, 2022)

Microcosmic Characteristics of Hydrate Formation and Decomposition in the Different Particle Size Sediments Captured by Cryo-SEM - Jingsheng Lu; Decai Lin; Dongliang Li; Deqing Liang; Long Wen; Siting Wu; Yiqun Zhang; Yong He; Lingli Shi; Youming Xiong (Journal of Marine Science and Engineering, 2022)
Sand production and sand control studies in non-diagenetic reservoirs are the weak point in the conventional petroleum industry. However, natural gas hydrate (NGH) mainly exists in non-diagenetic strata, and sand production occurs during exploitation, which restricts the safe and sustainable production of NGH. To study the microcosmic characteristics of sand production, the hydrate decomposition behaviours in the sediments were captured by the Cryo-SEM method. The micromorphology of different particle sizes of sand samples containing NGH (the sand median diameter d50 is 150, 87, 55, 38, 24, and 13 µm) and the microcosmic processes of NGH decomposition were observed. Then, the microcosmic characteristics of sand production, during the decomposition process, were analysed. (1) The gas hydrate decomposition increases pore space and reduces reservoir strength; the expansion action of the decomposition of water and gas, the softening action of the decomposition of water, and the compression action by overlying stress (crustal stress) promoted sand production, deformation, and subsidence of the NGH reservoirs in the mining process. (2) The decomposition of NGH has a more significant impact on sediments with smaller particle sizes. (3) The particle size of NGH may be larger than the particle size of the mud in the reservoirs, and acting as “gravel” plays a particular role in sand control. Therefore, the particle size of NGH cannot be ignored in the design of sand control. (4) It has been revealed, and verified, that sputtering (splashing) is a unique process of sand production caused by NGH decomposition. In other words, the rapid expansion of the volume of the decomposed gas and water from NGH leads to the eruption and sputtering of hydrate particles, providing the driving force for sand migration, which is a different process of sand production than in conventional oil and gas.

Simultaneous determination of praziquantel and its main metabolites in the tissues of black goats and their residue depletion - Tong-Yan Ding; Xiao-Gui Shu; Ren-Ping Xiong; Jing-Li Qiu; Lu Li; Li-Min He (Food Additives & Contaminants: Part A, 2022)

Simulation of the pollution abatement behavior of regional metal-related enterprises based on the interactive perspective of industrial agglomerations and emission reduction effects - Li-Xin Xiong; Jia-Jun Ning; Yun-He Dong; Meng-Meng Dai (Environmental Geochemistry and Health, 2022)

Sorption and desorption of sex hormones in soil- and sediment-water systems: A review - Xiong Dai; Xingjian Yang; Bihai Xie; Jiajia Jiao; Xiuping Jiang; Chengyu Chen; Zhen Zhang; Zhili He; Hang Lin; Weisong Chen; Yongtao Li (Soil Ecology Letters, 2022)

Zinc Protects against Heat Stress–Induced Apoptosis via the Inhibition of Endoplasmic Reticulum Stress in TM3 Leydig Cells - Yongjie Xiong; Jing Li; Shaojun He (Biological Trace Element Research, 2022)

Flood vulnerability assessment using the triangular fuzzy number-based analytic hierarchy process and support vector machine model for the Belt and Road region - Yu Duan; Junnan Xiong; Weiming Cheng; Nan Wang; Yi Li; Yufeng He; Jun Liu; Wen He; Gang Yang (Natural Hazards, 2022)

Driving forces for recovery of forest vegetation after harvesting a subalpine oak forest in eastern Tibetan Plateau - Qinli Xiong; Lingjuan Li; Xiaojin Luo; Xingjin He; Lin Zhang; Kaiwen Pan; Chenggang Liu; Hui Sun (Environmental Science and Pollution Research, 2021)

AFAP1-AS1: a rising star among oncogenic long non-coding RNAs - Fang Xiong; Kunjie Zhu; Su Deng; Hongbin Huang; Liting Yang; Zhaojian Gong; Lei Shi; Yi He; Yanyan Tang; Qianjin Liao; Jianjun Yu; Xiaoling Li; et al. (Science China Life Sciences, 2021)

Biopolymer-based flocculants: a review of recent technologies - Xincheng Jiang; Yisen Li; Xiaohui Tang; Junyi Jiang; Qiang He; Zikang Xiong; Huaili Zheng (Environmental Science and Pollution Research, 2021)

Investigation of the strength recovery characteristics of a red-bed landslide soil by SHS and ultrasonic experiments - Qiwei Yan; Xinpo Li; Xiong Tang; Yong Wu; Siming He (Bulletin of Engineering Geology and the Environment, 2021)

Molecular surveillance of coxsackievirus A16 in southern China, 2008–2019 - Lina Yi; Hanri Zeng; Huanying Zheng; Jinju Peng; Xue Guo; Leng Liu; Qianling Xiong; Limei Sun; Xiaohua Tan; Jianfeng He; Jing Lu; Hui Li (Archives of Virology, 2021)

Different effects of sheep excrement type and supply level on plant and soil C:N:P stoichiometry in a typical steppe on the loess plateau - Lan Li; Jing Zhang; Xiong Zhao He; Fujiang Hou (Plant and Soil, 2021)

Evaluating the Potentiality of Using Control-free Images from a Mini Unmanned Aerial Vehicle (UAV) and Structure-from-Motion (SfM) Photogrammetry to Measure Paleoseismic Offsets - Xue Li; Baosong Xiong; Zhaode Yuan; Kefeng He; Xiaoli Liu; Zhumei Liu; Zhaoqing Shen (International Journal of Remote Sensing, 2021)

Structure of SARS-CoV-2 main protease in the apo state - Xuelan Zhou; Fanglin Zhong; Cheng Lin; Xiaohui Hu; Yan Zhang; Bing Xiong; Xiushan Yin; Jinheng Fu; Wei He; Jingjing Duan; Yang Fu; Huan Zhou; et al. (Science China Life Sciences, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Diversity and Composition of Gut Bacterial Community in Giant Panda with Anorexia - Siyue Zhao; Caiwu Li; Tao Zhu; Lei Jin; Wenwen Deng; Ke Zhao; Yongguo He; Guo Li; Yaowu Xiong; Ti Li; Bei Li; Yan Huang; et al. (Current Microbiology, 2021)

miR-23b Attenuates LPS-Induced Inflammatory Responses in Acute Lung Injury via Inhibition of HDAC2 - Zhi-Feng Luo; Xiang-Hui Jiang; Huan Liu; Li-Yuan He; Xiong Luo; Fu-Chun Chen; Yu-Lin Tan (Biochemical Genetics, 2021)

Rare taxa maintain the stability of crop mycobiomes and ecosystem functions - Chao Xiong; Ji‐Zheng He; Brajesh K. Singh; Yong‐Guan Zhu; Jun‐Tao Wang; Pei‐Pei Li; Qin‐Bing Zhang; Li‐Li Han; Ju‐Pei Shen; An‐Hui Ge; Chuan‐Fa Wu; Li‐Mei Zhang (Environmental Microbiology, 2021)
Summary Plants harbour highly diverse mycobiomes which sustain essential functions for host health and productivity. However, ecological processes that govern the plant–mycobiome assembly, interactions and their impact on ecosystem functions remain poorly known. Here we characterized the ecological role and community assembly of both abundant and rare fungal taxa along the soil–plant continuums (rhizosphere, phyllosphere and endosphere) in the maize–wheat/barley rotation system under different fertilization practices at two contrasting sites. Our results indicate that mycobiome assembly is shaped predominantly by compartment niche and host species rather than by environmental factors. Moreover, crop‐associated fungal communities are dominated by few abundant taxa mainly belonging to Sordariomycetes and Dothideomycetes, while the majority of diversity within mycobiomes are represented by rare taxa. For plant compartments, the abundant sub‐community is mainly determined by stochastic processes. In contrast, the rare sub‐community is more sensitive to host selection and mainly governed by deterministic processes. Furthermore, our results demonstrate that rare taxa play an important role in fungal co‐occurrence network and ecosystem functioning like crop yield and soil enzyme activities. These results significantly advance our understanding of crop mycobiome assembly and highlight the key role of rare taxa in sustaining the stability of crop mycobiomes and ecosystem functions.

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

Treatment of CML-transformed B Cell Acute Lymphoblastic Leukemia (B-ALL) in Adults with Anti-CD19 Chimeric Antigen Receptor T Cell (CAR T) Therapy - Fang Liu; Sha Sha; Gina Ma; Yi Su; Yisong Xiong; Guangcui He; Yecheng Li; William M. Hanes; William Tse (Stem Cell Reviews and Reports, 2020)

TGF-β regulation of microRNA miR-497-5p and ocular lens epithelial cell mesenchymal transition - Jinda Wang; Jingshang Zhang; Ying Xiong; Jing Li; Xiaoxia Li; Jing Zhao; Guyu Zhu; Hailong He; Yusufu Mayinuer; Xiuhua Wan (Science China Life Sciences, 2020)

Influence of complex topography on magnetotelluric-observed data using three-dimensional numerical simulation: A case from Guangxi area, China - Xiong Bin; Luo Tian-Ya; Chen Long-Wei; Dai Shi-Kun; Xu Zhi-Feng; Li Chang-Wei; Ding Yan-Li; Wang Hong-Hua; Li Jing-He (Applied Geophysics, 2020)

Characterization of heat stress affecting the growth performance, blood biochemical profile, and redox status in male and female broilers at market age - Shaojun He; Qirun Yin; Yongjie Xiong; Jing Li; Deyi Liu (Tropical Animal Health and Production, 2020)

An accelerated solvent extraction and gas chromatography-flame ionization detector method to rapidly determining and assessing total petroleum hydrocarbon contamination in soil from Fushan oilfield, China - Tengya Li; Xiaocong Cao; Shuhai He; Mingshan Zhang; Wenshuai Xu; Zengheng Xiong; Yan Liang; Chenye Wang; Biaojuan Chen (Environmental Science and Pollution Research, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Experimental investigation for dynamic instability of coal-rock masses in horizontal section mining of steeply inclined coal seams - Zheng-yi Wang; Lin-ming Dou; Jiang He; An-ye Cao; Xiong-wei Li; Peng-bo Li; Chang-sheng Wu (Arabian Journal of Geosciences, 2020)

Expression and regulation of Smad2 by gonadotropins in the protogynous hermaphroditic ricefield eel (Monopterus albus) - Zhi He; Faqiang Deng; Sen Xiong; Yueping Cai; Zhide He; Xiongyan Wang; Song Li; Deying Yang; Taiming Yan (Fish Physiology and Biochemistry, 2020)

Path Following of a Water-Jetted USV Based on Maneuverability Tests - Junmin Mou; Yangying He; Benren Zhang; Shixuan Li; Yong Xiong (Journal of Marine Science and Engineering, 2020)
Due to the high propulsive efficiency and better maneuverability under high speed, the water-jetted unmanned surface vehicle (USV) is widely studied and used. This paper presents complete maneuvering tests and control algorithm designed for a twin water-jetted USV model. Firstly, a wireless network control platform is established, and maneuvering tests, for instance, an inertia test, zig-zag test and turning test, are carried out to verify the maneuverability of the USV. In light of the complexity and uncertainty of ship sailing and ship handling, the Human Simulated Intelligent Control (HSIC) method is utilized to optimize the response time, accuracy and robustness of the controller. Finally, for the path following and track rectification part, a Line of Sight (LOS) algorithm is improved and proved practicable with triangle/square path tests. The proposed intelligent navigation algorithm specially designed for matching with the control methods, showing satisfactory improvements on the motion control and path following of the specific USV.

Bamboo nutrients and microbiome affect gut microbiome of giant panda - Lei Jin; Daifu Wu; Caiwu Li; Anyun Zhang; Yaowu Xiong; Rongping Wei; Guiquan Zhang; Shengzhi Yang; Wenwen Deng; Ti Li; Bei Li; Xin Pan; et al. (Symbiosis, 2020)

Epidemic and genetic characterization of porcine epidemic diarrhea virus strains circulating in the regions around Hunan, China, during 2017-2018 - Lei Tan; Yalan Li; Jiayi He; Yi Hu; Xiong Cai; Wei Liu; Tanbing Liu; Jiaoshun Wang; Zhoumian Li; Xiaoming Yuan; Yang Zhan; Lingchen Yang; et al. (Archives of Virology, 2020)

Enhancement of the sewage sludge dewaterability by using ethanol and Fe(III)-rice husk - Lei Chen; Qiao Xiong; He Li; Haobo Hou; Min Zhou (Environmental Science and Pollution Research, 2020)

Methods of extraction, separation, purification, structural characterization for polysaccharides from aquatic animals and their major pharmacological activities - Qingping Xiong; Zhuoyue Song; Weihui Hu; Jian Liang; Yi Jing; Lian He; Song Huang; Xiaoli Wang; Shaozhen Hou; Tingting Xu; Jing Chen; Danyan Zhang; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Phytohalomonas tamaricis gen. nov., sp. nov., an endophytic bacterium isolated from Tamarix ramosissima roots growing in Kumtag desert - Lei Liu; Shi-yan Wang; Cong-fen He; Xiao-xia Zhang; Miao Chi; Li-xiong Liang; Lu-bin Li (Archives of Microbiology, 2020)

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

LASG Global AGCM with a Two-moment Cloud Microphysics Scheme: Energy Balance and Cloud Radiative Forcing Characteristics - Lei Wang; Qing Bao; Wei-Chyung Wang; Yimin Liu; Guo-Xiong Wu; Linjiong Zhou; Jiandong Li; Hua Gong; Guokui Nian; Jinxiao Li; Xiaocong Wang; Bian He (Advances in Atmospheric Sciences, 2019)

Correction to: Ready player one? Autophagy shapes resistance to photodynamic therapy in cancers - Xian Duan; Bo Chen; Yanan Cui; Lin Zhou; Chenkai Wu; Zhulin Yang; Yu Wen; Xiongying Miao; Qinglong Li; Li Xiong; Jun He (Apoptosis, 2019)

Evaluation of a Potential Clinical Significant Drug-Drug Interaction between Digoxin and Bupropion in Cynomolgus Monkeys - Yang Shen; Yang Yu; Wei Lai; Shuai Li; Zixuan Xu; Jiejing Jin; Xia Yan; Han Xing; Xijing Chen; Aizhen Xiong; Chunhua Xia; Jiake He; et al. (Pharmaceutical Research, 2019)

Ready player one? Autophagy shapes resistance to photodynamic therapy in cancers - Xian Duan; Bo Chen; Yanan Cui; Lin Zhou; Chenkai Wu; Zhulin Yang; Yu Wen; Xiongying Miao; Qinglong Li; Li Xiong; Jun He (Apoptosis, 2018)

Changes in gene and genotype frequencies during the development of the grass carp Ctenopharyngodon idella - LiB. He; Lv Xiong; AiD. Zhang; YongM. Li; Rong Huang; LanJ. Liao; ZuoY. Zhu; YaP. Wang (Journal of Fish Biology, 2018)
In this study, a full‐sib population of Ctenopharyngodon idella was constructed and approximately 500 C. idella individuals were sampled at four early developmental stages (hatching, first feeding, juvenile fish and young fish). Four DNA pools were constructed and subjected to next‐generation sequencing. On the basis of the identification of single nucleotide polymorphisms (SNP), changes in gene and genotype frequencies during the developmental progress of C. idella were revealed, which indicates that death during the early developmental stage is not a random process. These findings will establish the basis for further studies performed for identifying superior alleles or genotypes as target markers for molecular breeding.

Genetic characterization and fine mapping for multi-inflorescence in Brassica napus L. - Yongjing Zhang; Qinfei Li; Yixin Cui; Zhi Liu; Zhifu Chen; Yajun He; Jiaqin Mei; Qing Xiong; Xiaorong Li; Wei Qian (Theoretical and Applied Genetics, 2018)

Triterpenoid saponins from the buds of Lonicera similis - Xiao Zhang; Li-Hua Zou; Yu-Lin He; Cheng Peng; Li Guo; Liang Xiong (Natural Product Research, 2018)

Cadmium-accumulator straw application alleviates cadmium stress of lettuce (Lactuca sativa) by promoting photosynthetic activity and antioxidative enzyme activities - Yi Tang; Yongdong Xie; Guochao Sun; Huaqiang Tan; Lijin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Xiulan Lv; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2018)

Phagocytosis Deficiency of Macrophages in NOD.H-2h4 Mice Accelerates the Severity of Iodine-Induced Autoimmune Thyroiditis - Xue He; Chuhui Xiong; Aihua Liu; Wei Zhao; Xinghai Xia; Shiqiao Peng; Chenyan Li; Mi Zhou; Yushu Li; Xiaoguang Shi; Zhongyan Shan; Weiping Teng (Biological Trace Element Research, 2018)

Purinergic P2X7 receptor functional genetic polymorphisms are associated with the susceptibility to osteoporosis in Chinese postmenopausal women - Hong Xu; Chengxin Gong; Luling He; Shenqiang Rao; Xingzi Liu; Yijun Nie; Changle Liu; Tao Li; Lu Ding; Yunming Tu; Yuping Yang; Fangfang Hu; et al. (Purinergic Signalling, 2017)

DNA hypermethylation of sFRP5 contributes to indoxyl sulfate-induced renal fibrosis - Yanlin Yu; Xu Guan; Ling Nie; Yong Liu; Ting He; Jiachuan Xiong; Xinli Xu; Yan Li; Ke Yang; Yiqin Wang; Yunjian Huang; Bing Feng; et al. (Journal of Molecular Medicine, 2017)

Cryopreservation of Jerusalem artichoke cultivars using an improved droplet-vitrification method - Jin-Mei Zhang; Li Han; Xin-Xiong Lu; Gayle M. Volk; Xia Xin; Guang-Kun Yin; Juan-Juan He; Ling Wang; Xiao-Ling Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

Long-Term Selenium-Deficient Diet Induces Liver Damage by Altering Hepatocyte Ultrastructure and MMP1/3 and TIMP1/3 Expression in Growing Rats - Jing Han; Hua Liang; Jianhua Yi; Wuhong Tan; Shulan He; Sen Wang; Feng Li; Xiaofang Wu; Jing Ma; Xiaowei Shi; Xiong Guo; Chuanyi Bai (Biological Trace Element Research, 2017)

Effects of Replacing of Inorganic Trace Minerals by Organically Bound Trace Minerals on Growth Performance, Tissue Mineral Status, and Fecal Mineral Excretion in Commercial Grower-Finisher Pigs - Bing Liu; Pingwen Xiong; Nana Chen; Junna He; Gang Lin; Yan Xue; Weifen Li; Dongyou Yu (Biological Trace Element Research, 2016)

A new flavane acid from the fruits of Illicium verum - Liang-Deng Wu; Chun-Lan Xiong; Zi-Zhan Chen; Rui-Jie He; Yan-Jun Zhang; Yan Huang; Sheng-Ping Deng; Rui-Yun Yang; Jun Li (Natural Product Research, 2016)

LncRNA NONRATT021972 siRNA attenuates P2X7 receptor expression and inflammatory cytokine production induced by combined high glucose and free fatty acids in PC12 cells - Hong Xu; Luling He; Changle Liu; Lan Tang; Yonghu Xu; Mengqi Xiong; Mei Yang; Yongfang Fan; Fangfang Hu; Xingzi Liu; Lu Ding; Yun Gao; et al. (Purinergic Signalling, 2016)

Effect of Selenium Deficiency on Phosphorylation of the AMPK Pathway in Rats - Shulan He; Xiong Guo; Wuhong Tan; Xiaohui Su; Jiangping Li; Wang Pan; Hongyan Qiu (Biological Trace Element Research, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Responses of wheat and rice to factorial combinations of ambient and elevated CO 2 and temperature in FACE experiments - Chuang Cai; Xinyou Yin; Shuaiqi He; Wenyu Jiang; Chuanfei Si; Paul C. Struik; Weihong Luo; Gang Li; Yingtian Xie; Yan Xiong; Genxing Pan (Global Change Biology, 2016)
Elevated CO 2 and temperature strongly affect crop production, but understanding of the crop response to combined CO 2 and temperature increases under field conditions is still limited while data are scarce. We grew wheat ( Triticum aestivum L.) and rice ( Oryza sativa L.) under two levels of CO 2 (ambient and enriched up to 500 μmol mol −1 ) and two levels of canopy temperature (ambient and increased by 1.5–2.0 °C) in free‐air CO 2 enrichment (FACE) systems and carried out a detailed growth and yield component analysis during two growing seasons for both crops. An increase in CO 2 resulted in higher grain yield, whereas an increase in temperature reduced grain yield, in both crops. An increase in CO 2 was unable to compensate for the negative impact of an increase in temperature on biomass and yield of wheat and rice. Yields of wheat and rice were decreased by 10–12% and 17–35%, respectively, under the combination of elevated CO 2 and temperature. The number of filled grains per unit area was the most important yield component accounting for the effects of elevated CO 2 and temperature in wheat and rice. Our data showed complex treatment effects on the interplay between preheading duration, nitrogen uptake, tillering, leaf area index, and radiation‐use efficiency, and thus on yield components and yield. Nitrogen uptake before heading was crucial in minimizing yield loss due to climate change in both crops. For rice, however, a breeding strategy to increase grain number per m 2 and % filled grains (or to reduce spikelet sterility) at high temperature is also required to prevent yield reduction under conditions of global change.

Complete genome sequence of the first bluetongue virus serotype 7 isolate from China: evidence for entry of African-lineage strains and reassortment between the introduced and native strains - Heng Yang; Minna Lv; Minfei Sun; Liqin Lin; Meilin Kou; Lin Gao; Defang Liao; Heli Xiong; Yuwen He; Huachun Li (Archives of Virology, 2016)

Influence of Val108/158Met COMT Gene Polymorphism on the Efficacy of Modified Electroconvulsive Therapy in Patients with Treatment Resistant Depression - Zhaoyu Lin; Hongbo He; Chunping Zhang; Zhijie Wang; Miaoling Jiang; Qirong Li; Xiaochang Lan; Minling Zhang; Xiong Huang (Cell Biochemistry and Biophysics, 2015)

Toxic effects of HgCl2 on activities of SOD, AchE and relative expression of SOD, AChE, CYP1A1 of zebrafish - He Zhen; Mu Wen; Yang Yang; Zhang Can; Geng Hui; Xiong Li; Liu Deli (Ecotoxicology, 2014)

Influence of BBP exposure on nervous system and antioxidant system in zebrafish - Can Zhang; Xue Yang; Zhen He; Qiu Zhong; Jia Guo; Xiao-jing Hu; Li Xiong; Deli Liu (Ecotoxicology, 2014)

Downregulation of miR-133 via MAPK/ERK signaling pathway involved in nicotine-induced cardiomyocyte apoptosis - Lu Wang; Xuelian Li; Yuhong Zhou; Hui Shi; Chaoqian Xu; Hua He; Shuxuan Wang; Xuehui Xiong; Yong Zhang; Zhimin Du; Ruixue Zhang; Yanjie Lu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Exploring the pattern of phenotypic and genetic polymorphism in the arsenic hyperaccumulator Pteris vittata L. (Chinese brake fern) - Bing Yang; Alessio Mengoni; Ye-Ling Huang; Xiong-Lei He; Jin-Tian Li; Bin Liao; Mi Zhou; Wen-Sheng Shu (Plant and Soil, 2013)

Glycosylation analysis of recombinant neutral protease I from Aspergillus oryzae expressed in Pichia pastoris - Da Lei; Yang Xu; Qinghua He; Yifeng Pan; Bo Chen; Liang Xiong; Yanping Li (Biotechnology Letters, 2013)

Molecular Profiling of Genetic Variability in Domesticated Groundnut (Arachis hypogaea L.) Based on ISJ, URP, and DAMD Markers - Faqian Xiong; Junxian Liu; Jing Jiang; Ruichun Zhong; Liangqiong He; Zhuqiang Han; Zhong Li; Xiumei Tang; Ronghua Tang (Biochemical Genetics, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Comparing gene expression profiles of Kashin-Beck and Keshan diseases occurring within the same endemic areas of China - Xi Wang; Shuang Wang; ShuLan He; Feng Zhang; WuHong Tan; YanXia Lei; HanJie Yu; Zheng Li; YuJie Ning; YouZhang Xiang; Xiong Guo (Science China Life Sciences, 2013)

New kaurene diterpenoid glycosides from fenugreek seeds - Xu Pang; Li-Ping Kang; He-Shui Yu; Yang Zhao; Cheng-Qi Xiong; Jie Zhang; Bai-Ping Ma (Natural Product Research, 2013)

Saccharomonospora oceani sp. nov. isolated from marine sediments in Little Andaman, India - Dao-Feng Zhang; Wei Chen; Jie He; Xiao-Mei Zhang; Zi-jun Xiong; Maloy Kumar Sahu; Kannan Sivakumar; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Expression analysis, single nucleotide polymorphisms and combined genotypes in candidate genes and their associations with growth and carcass traits in Qinchuan cattle - Li-jun Wang; Xiao-lin Liu; Hong-liang Wang; Hua He; Zhi-xiong Li; Ling Chen (Molecular Biology Reports, 2013)

High levels of glucose induce “metabolic memory” in cardiomyocyte via epigenetic histone H3 lysine 9 methylation - Xi-Yong Yu; Yong-Jian Geng; Jia-Liang Liang; Saidan Zhang; He-Ping Lei; Shi-Long Zhong; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yangxin Li (Molecular Biology Reports, 2012)

Characterization of acute renal allograft rejection by proteomic analysis of renal tissue in rat - Gang Chen; Jing-bin Huang; Jie Mi; Yun-feng He; Xiao-hou Wu; Chun-li Luo; Si-min Liang; Jia-bing Li; Ya-xiong Tang; Jie Li (Molecular Biology Reports, 2012)

Characterization of an inositol 1,3,4-trisphosphate 5/6-kinase gene that is essential for drought and salt stress responses in rice - Hao Du; Linhong Liu; Lei You; Mei Yang; Yubing He; Xianghua Li; Lizhong Xiong (Plant Molecular Biology, 2011)

Effects of Schisandra sphenanthera extract on the blood concentration of tacrolimus in renal transplant recipients - Hua-Wen Xin; Qing Li; Xiao-Chun Wu; Yan He; Ai-Rong Yu; Lei Xiong; Ying Xiong (European Journal of Clinical Pharmacology, 2011)

Evidence of internal-wave and internal-tide deposits in the Middle Ordovician Xujiajuan Formation of the Xiangshan Group, Ningxia, China - You-Bin He; Jin-Xiong Luo; Xiang-Dong Li; Zhen-Zhong Gao; Zhan Wen (Geo-Marine Letters, 2011)

The myb transcription factor MdMYB6 suppresses anthocyanin biosynthesis in transgenic Arabidopsis - Jian-Jie Gao; Xue-Fang Shen; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jing Xu; Bo Zhu; Jian-Li Zheng; Quan-Hong Yao (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

The impact of positive cancer family history on the clinical features and outcome of patients with non-small cell lung cancer - Ning Li; Kang Shao; Zhaoli Chen; Bin Qiu; Zhen Wang; Fengwei Tan; Jiwen Wang; Xiaogang Tan; Baozhong Li; Meihua Xiong; Fang Zhou; Jie He (Familial Cancer, 2011)

Genetic Diversity and Identity of Chinese Loquat Cultivars/Accessions (Eriobotrya japonica) Using Apple SSR Markers - Qiao He; Xiong Wei Li; Guo Lu Liang; Kun Ji; Qi Gao Guo; Wei Min Yuan; Gen Zhi Zhou; Kun Song Chen; W. Eric van de Weg; Zhong Shan Gao (Plant Molecular Biology Reporter, 2011)

Molecular characterization and association analysis of porcine adipose triglyceride lipase (PNPLA2) gene - Li He Dai; Yuan Zhu Xiong; Si Wen Jiang; Jun Feng Chen (Molecular Biology Reports, 2011)

Stress responsive gene CIPK14 is involved in phytochrome A-mediated far-red light inhibition of greening in Arabidopsis - YuZhi Qin; Ming Guo; Xu Li; XingYao Xiong; ChangZheng He; XianZhou Nie; XuanMing Liu (Science China Life Sciences, 2010)

Geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced human umbilical vein endothelial cells by blocking p38 and ERK1/2 signaling pathways - Hong-Tao Liu; Jun-Lin He; Wen-Ming Li; Zhu Yang; Ying-Xiong Wang; Juan Yin; Yu-Guang Du; Chao Yu (Inflammation Research, 2010)

Tillage pedogenesis of purple soils in southwestern China - Xiubin He; Yuhai Bao; Hongwei Nan; Donghong Xiong; Li Wang; Yanfeng Liu; Jingbo Zhao (Journal of Mountain Science, 2009)

Test of deep seismic reflection profiling across central uplift of Qiangtang terrane in Tibetan plateau - Zhanwu Lu; Rui Gao; Qiusheng Li; Rizheng He; Chaoyang Kuang; Hesheng Hou; Xiaosong Xiong; Ye Guan; Haiyan Wang; S. L. Klemperer (Journal of Earth Science, 2009)

Gastric carcinoma with osteoclast-like giant cells: a case report and review of the literature - Li-duan Zheng; Xiu-ping Yang; Hua-xiong Pan; Xiu Nie; Jun He; Qing Lv; Qiang-song Tong (Journal of Zhejiang University-SCIENCE B, 2009)

Association study of the oestrogen signalling pathway genes in relation to age at natural menopause - Li-Na He; Dong-Hai Xiong; Yong-Jun Liu; Feng Zhang; Robert R. Recker; Hong-Wen Deng (Journal of Genetics, 2007)

Isolation and characterization of a novel cDNA encoding ERF/AP2-type transcription factor OsAP25 from Oryza Sativa L. - Xiao-Yan Fu; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jin-Ge Liu; Li-Juan Wu; Feng Gao; Hong Zhu; Zhao-Kui Guo; Quan-Hong Yao (Biotechnology Letters, 2007)

Antiviral activity of arbidol against influenza A virus, respiratory syncytial virus, rhinovirus, coxsackie virus and adenovirus in vitro and in vivo - L. Shi; H. Xiong; J. He; H. Deng; Q. Li; Q. Zhong; W. Hou; L. Cheng; H. Xiao; Z. Yang (Archives of Virology, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

An improved system to establish highly embryogenic haploid cell and protoplast cultures from pollen calluses of maize (Zea mays L.) - Guangyuan He; Jinrui Zhang; Kexiu Li; Zhiyong Xiong; Mingjie Chen; Junli Chang; Yuesheng Wang; Guangxiao Yang; Beáta Barnabás (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Dynamics of zinc uptake and accumulation in the hyperaccumulating and non-hyperaccumulating ecotypes of Sedum alfredii Hance - X. E. Yang; T. Q Li; X. X. Long; Y. H. Xiong; Z. L. He; P. J. Stoffella (Plant and Soil, 2006)

Codon-modifications and an endoplasmic reticulum-targeting sequence additively enhance expression of an Aspergillus phytase gene in transgenic canola - Ri-He Peng; Quan-Hong Yao; Ai-Sheng Xiong; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2006)

Vitreoscilla hemoglobin overexpression increases submergence tolerance in cabbage - Xian Li; Ri-He Peng; Hui-Qin Fan; Ai-Sheng Xiong; Quan-Hong Yao; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2005)

Different effects on ACC oxidase gene silencing triggered by RNA interference in transgenic tomato - Ai-Sheng Xiong; Quan-Hong Yao; Ri-He Peng; Xian Li; Pei-Lai Han; Hui-Qin Fan (Plant Cell Reports, 2005)